Water-based coating composition

The use of specialized aqueous coating compositions with urethane resin particles and reactive resins in a 3-coat, 1-bake process improves glass adhesion and image clarity in multilayer automotive coatings, overcoming mixing issues and temperature constraints.

JP7602310B2Active Publication Date: 2024-12-18KANSAI PAINT CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021012542
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-29
Publication Date
2024-12-18
Estimated Expiration
2041-01-29

AI Technical Summary

Technical Problem

Existing 3-coat, 1-bake methods for forming multilayer coating films on automobile bodies face issues with paint layer mixing, inadequate glass adhesion, and insufficient image clarity, particularly when omitting preheating after applying water-based intermediate coatings.

Method used

Aqueous coating compositions containing urethane resin particles with specific film-forming and glass transition temperatures, combined with reactive group-containing resins and crosslinking agents, are applied in a 3-coat, 1-bake process at low temperatures to form multilayer coatings with enhanced adhesion and clarity.

Benefits of technology

The proposed method achieves multilayer coatings with excellent glass adhesion and image clarity, even at reduced curing temperatures, addressing the limitations of previous methods by ensuring clear and durable film formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602310000001
    Figure 0007602310000001
  • Figure 0007602310000002
    Figure 0007602310000002
  • Figure 0007602310000003
    Figure 0007602310000003
Patent Text Reader

Abstract

To provide a water-based coating composition that can form a multi-layer coating film having excellent adhesion to glass and excellent image clarity.SOLUTION: Provided is a water-based coating composition that contains a urethane resin particle (A) having a minimum film-forming temperature in the range of -20 to 50°C and a glass transition temperature in dynamic viscoelasticity measurement at a frequency of 1 Hz in the range of 60 to 120°C, a reactive group-containing resin (B) and a cross-linking agent (C). The urethane resin particle (A) has a breaking elongation at -20°C in the range of 200 to 350%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aqueous coating composition. [Background technology]

[0002] In recent years, environmental issues have attracted great attention on a global scale, and the automobile industry has also been actively working to improve the environment in its production processes. The automobile manufacturing process can cause problems such as global warming, industrial waste, and emissions of volatile organic solvents (VOCs), and most VOCs are generated during the painting process, making measures to address this issue urgently needed.

[0003] The widely adopted method of forming paint films on automobile bodies is to apply electrodeposition coating to the substrate, followed by a three-coat, two-bake (3C2B) process of "painting the intermediate coat paint → baking hardening → painting the water-based base coat paint → preheating (preheating) → painting the clear coat paint → baking hardening" to form a multi-layer paint film. However, in recent years, from the perspective of saving energy and reducing VOCs, attempts have been made to use a water-based intermediate coat paint as the intermediate coat paint, omitting the baking hardening process after painting the water-based intermediate coat paint, and instead applying electrodeposition coating to the substrate, followed by a three-coat, one-bake (3C1B) process of "painting the water-based intermediate coat paint → preheating (preheating) → painting the water-based base coat paint → preheating (preheating) → painting the clear coat paint → baking hardening."

[0004] However, in the above-mentioned 3-coat 1-bake method, the intermediate coat layer and the base coat layer may become mixed with each other, making it difficult to obtain a multi-layer coating film with excellent image clarity, which has been a problem.

[0005] On the other hand, in the manufacturing specifications of automobiles, glass members such as a front glass and a rear glass generally have an adhesive layer formed on the above-mentioned clear coating film, and are fixed by the adhesive.

[0006] Patent Document 1 describes a method for forming a multilayer coating film on an electrodeposition-coated galvannealed steel sheet by sequentially carrying out the following steps (1) to (4): step (1): applying a water-based intermediate coating paint (A) onto the electrodeposition coating film to form an intermediate coating film; step (2): applying a water-based base coating paint (B) onto the intermediate coating film after preheating to form a base coating film; step (3): applying a clear coating paint (C) onto the base coating film after preheating to form a clear coating film; step (4): A step of heat-curing the intermediate coating film, the base coating film and the clear coating film formed in the steps (1) to (3); the water-based intermediate coating paint (A) is a polyurethane resin (a2) having a glass transition temperature (Tg) in the range of 5 to 15°C and a weight average molecular weight in the range of 30,000 to 40,000, a polyurethane resin (a3) ​​having a glass transition temperature (Tg) of -50°C or lower and a polyether skeleton, and a hydroxyl group-containing polyester resin (a4). a hydroxyl-containing acrylic resin (a1) and a polyurethane resin (a2) in a ratio of 20 / 10 to 30 / 10 in terms of solid content; a coating film formed by heat curing with the water-based undercoat paint (A) has a breaking elongation at 20°C in a range of 20 to 30%, a Young's modulus in a range of 5,000 to 6,000 kgf / cm2, and a Tukon hardness in a range of 4 to 6; and the clear paint (C) contains a hydroxyl-containing acrylic resin (c1) and an allophanate-containing polyisocyanate compound (c2). This method for forming a multilayer coating film is characterized in that it contains a melamine resin (a4) and an active methylene-blocked polyisocyanate compound (a5), and the ratio of the hydroxyl-containing acrylic resin (a1) and the polyurethane resin (a2) is within a range of 20 / 10 to 30 / 10 in terms of solid content ratio, and the coating film formed by heat curing with the water-based undercoat paint (A) has a breaking elongation at 20°C in a range of 20 to 30%, a Young's modulus in a range of 5,000 to 6,000 kgf / cm2, and a Tukon hardness in a range of 4 to 6.

[0007] Furthermore, recently, from the viewpoint of further energy saving, it has been desired to further lower the heating temperature in the bake hardening step.

[0008] In addition, in order to further reduce the energy used, it is also desirable to omit the preheating step after application of the water-based intermediate coating in the above-mentioned 3-coat 1-bake (3C1B) system. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent Publication 2019-198861 Summary of the Invention [Problem to be solved by the invention]

[0010] In the technique described in Patent Document 1, the adhesive strength when adhering a glass member to the multilayer coating film formed (hereinafter, sometimes referred to as "glass adhesion") was insufficient in some cases.

[0011] Furthermore, in the technique described in Patent Document 1, the multi-layer coating film formed sometimes had insufficient image sharpness.

[0012] An object of the present invention is to provide an aqueous coating composition capable of forming a multi-layer coating film having excellent adhesion to glass and excellent image clarity. [Means for solving the problem]

[0013] As a result of extensive investigations to achieve the above-mentioned object, the inventors have found that the above-mentioned object can be achieved by an aqueous coating composition containing urethane resin particles (A) having a minimum film-forming temperature in the range of -20 to 50°C and a glass transition temperature in the range of 60 to 120°C as measured by dynamic viscoelasticity at a frequency of 1 Hz, a reactive group-containing resin (B) and a crosslinking agent (C).

[0014] That is, the present invention provides the following <1> ~ <14> This is regarding. <1> An aqueous coating composition comprising urethane resin particles (A) having a minimum film-forming temperature in the range of -20 to 50°C and a glass transition temperature in the range of 60 to 120°C as measured by dynamic viscoelasticity at a frequency of 1 Hz, a reactive group-containing resin (B) and a crosslinking agent (C). <2> The urethane resin particles (A) have a breaking elongation at −20° C. in the range of 200 to 350%. <1> The aqueous coating composition according to claim 1. <3> The polyol component (a1) of the urethane resin particles (A) contains the polyol component (A1) having a melting point of 40 to 80°C. <1> or <2> The aqueous coating composition according to claim 1. <4> The polyol component (a1) of the urethane resin particles (A) contains a polycarbonate polyol (a1-1). <1> ~ <3> 13. The aqueous coating composition according to claim 12 . <5> The polyol component (a1) of the urethane resin particles (A) contains a polycarbonate diol obtained from a diol component containing an alicyclic diol having a cycloalkylene group having 6 or more carbon atoms. <1> ~ <4> 13. The aqueous coating composition according to claim 12 . <6> The urethane resin particles (A) are urethane resin particles (A') having a core-shell structure. <1> ~ <5> 13. The aqueous coating composition according to claim 12 . <7> The polyol component (a'1-I) of the urethane resin constituting the core part of the urethane resin particle (A') having a core-shell structure contains a polyether polyol (a1-2). <6> The aqueous coating composition according to claim 1. <8> The polyol component (a'1-II) of the urethane resin constituting the shell portion of the urethane resin particles (A') having a core-shell structure contains a polycarbonate polyol (a1-1). <6> or <7> The aqueous coating composition according to claim 1. <9> In the urethane resin particles (A') having a core-shell structure, a mass ratio (a'1-I) / (a'1-II) of the polyol component (a'1-I) of the urethane resin constituting the core part to the polyol component (a'1-II) of the urethane resin constituting the shell part is within a range of 60 / 40 to 20 / 80. <6> ~ <8> 13. The aqueous coating composition according to claim 12 . <10> The reactive group-containing resin (B) contains a hydroxyl group-containing resin (B'). <1> ~ <9> 13. The aqueous coating composition according to claim 12 . <11> The crosslinking agent (C) contains at least one crosslinking agent selected from an amino resin, a polyisocyanate compound, and a blocked polyisocyanate compound. <1> ~ <10> 13. The aqueous coating composition according to claim 12 . <12> On the object to be coated, <1> ~ <11> 2. A method for forming a coating film, comprising: applying the aqueous coating composition according to any one of the above items to form an uncured colored coating film; and then heating the uncured colored coating film at a temperature within the range of 60 to 110°C to cure it. <13> Step (II-1): A step of applying a colored coating composition (X) to a substrate to form an uncured colored coating film; Step (II-2): A step of applying a base coat paint composition (Y) onto the uncured colored coating film to form an uncured base coat coating film; Step (II-3): A step of applying a clear coat paint composition (Z) onto the uncured base coat film to form an uncured clear coat film; and Step (II-4): A method for forming a multilayer coating film, comprising a step of heating the uncured colored coating film, the uncured base coat coating film and the uncured clear coat coating film to simultaneously cure them, wherein the colored coating composition (X) is <1> ~ <11> 2. A method for forming a multi-layer coating film, comprising the aqueous coating composition according to claim 1 . <14> The heating temperature in the step (II-4) is within the range of 60 to 110°C. <13> The method for forming a multilayer coating film according to claim 1. Effect of the Invention

[0015] According to the aqueous coating composition of the present invention, a coating film excellent in glass adhesion and vividness can be formed. In particular, the aqueous coating composition of the present invention can form a multilayer coating film excellent in glass adhesion and vividness even when cured at a relatively low temperature. In addition, the aqueous coating composition of the present invention can form a multilayer coating film excellent in glass adhesion and vividness in a 3-coat 1-bake method in which an aqueous first colored coating, an aqueous second colored coating, and a clear coating are sequentially applied to a substrate, and the resulting three-layer multilayer coating film is simultaneously heated and cured. In particular, in the above 3-coat 1-bake method, a multilayer coating film excellent in glass adhesion and vividness can be formed even when cured at a relatively low temperature. Furthermore, a multilayer coating film having excellent glass adhesion and vividness can be formed even in a 3-coat 1-bake method in which preheating after application of the above aqueous first colored coating is omitted. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be described in detail below, however, these are examples of preferred embodiments and the present invention is not limited to the contents thereof.

[0017] [Water-based paint composition] The aqueous coating composition of the present invention contains urethane resin particles (A) having a minimum film-forming temperature in the range of -20 to 50°C and a glass transition temperature in the range of 60 to 120°C as measured by dynamic viscoelasticity at a frequency of 1 Hz, a reactive group-containing resin (B) and a crosslinking agent (C).

[0018] In this specification, the term "water-based paint" is a term that is contrasted with organic solvent-based paint, and generally means paint in which a film-forming resin, pigment, etc. are dispersed and / or dissolved in water or a medium mainly composed of water (aqueous medium). The organic solvent-based paint is paint that does not substantially contain water as a solvent, or in which all or most of the solvent is an organic solvent.

[0019] [Urethane resin particles (A)] The urethane resin particles (A) have a minimum film-forming temperature in the range of -20 to 50°C and a glass transition temperature in the range of 60 to 120°C in dynamic viscoelasticity measurement at a frequency of 1 Hz.

[0020] The minimum film-forming temperature (MFT) of the urethane resin particles (A) is the lowest temperature at which a crack-free, uniform film is formed when the urethane resin particles (A) are dried, and can be measured by the method described in JIS K 6828-2: 2003. More specifically, the MFT can be determined by applying the urethane resin particles (A) to a dry film thickness of 50 μm, heating under a temperature gradient in the range of −25 to 90° C., and measuring the boundary temperature between the film-formed portion and the non-film-formed portion.

[0021] From the viewpoint of the sharpness of the coating film formed, the minimum film-forming temperature of the urethane resin particles (A) is preferably within the range of -20 to 50°C, more preferably within the range of -10 to 45°C, and even more preferably within the range of 0 to 40°C.

[0022] The glass transition temperature of the urethane resin particles (A) is the dynamic glass transition temperature measured as the temperature at which tan δ (loss modulus / storage modulus) shows a maximum value in dynamic viscoelasticity measurement performed at a frequency of 1 Hz and a heating rate of 4° C. / min using a viscoelasticity measuring device "DMA Q800" (manufactured by TA Instruments Japan Co., Ltd.). Here, the sample used for measuring the glass transition temperature of the urethane resin particles (A) is prepared as follows. First, the urethane resin particles (A) are applied to a polypropylene plate so that the dry film thickness is 50 μm, pre-dried under conditions of 80° C. for 30 minutes, and then dried under conditions of 140° C. for 60 minutes to form a dry coating film. Next, the obtained dry coating film is peeled off from the polypropylene plate, and the part without the end or defect is cut into a strip of 20 mm in length and 5 mm in width to be used as a sample.

[0023] The glass transition temperature of the urethane resin particles (A) measured at a frequency of 1 Hz in dynamic viscoelasticity is preferably within the range of 60 to 120°C, more preferably within the range of 70 to 110°C, and even more preferably within the range of 80 to 100°C, from the viewpoints of glass adhesion and hardness of the coating film to be formed.

[0024] Furthermore, the breaking elongation of the urethane resin particles (A) at -20°C is preferably within the range of 200 to 350%, more preferably within the range of 220 to 320%, and even more preferably within the range of 230 to 300%, from the viewpoints of chipping resistance and glass adhesion of the coating film to be formed.

[0025] In this specification, the breaking elongation of the urethane resin particles (A) at -20°C is a value measured using a tensile tester. Specifically, the urethane resin particles (A) are applied to a polypropylene plate so that the film thickness based on the dried coating is about 50 μm, pre-dried under conditions of 80°C for 30 minutes, and then dried under conditions of 140°C for 60 minutes to form a dried coating. Next, the obtained dried coating is peeled off from the polypropylene plate, and cut into strips of 30 mm in length and 5 mm in width at the end and at the part without defects to obtain a sample. Next, using "Tensilon UTM-II-20" (trade name, manufactured by Orientec Co., Ltd.), the sample is pulled in the longitudinal direction at -20°C with a pulling speed of 4 mm / min and a chuck distance of 20 mm until it breaks. The breaking elongation can be calculated from the following formula. Breaking elongation rate (%) = (chuck distance at break - chuck distance before test) / (chuck distance before test) x 100.

[0026] The urethane resin particles (A) may contain a hydroxyl group.

[0027] The urethane resin particles (A) can generally be obtained from components including a polyol component (a1), a polyisocyanate component (a2), and, if necessary, a compound having both an active hydrogen group and an ion-forming group as a water-dispersible group-imparting component.

[0028] Polyol component (a1) The polyol component (a1) is a compound having at least two hydroxyl groups in one molecule. Among them, from the viewpoint of the productivity of the urethane resin particles (A), the polyol component (a1) is preferably a diol having two hydroxyl groups in one molecule.

[0029] From the viewpoint of the glass adhesion of the coating film to be formed, the melting point of the polyol component (a1) is preferably within the range of 40 to 80°C, more preferably within the range of 45 to 70°C, and particularly preferably within the range of 48 to 60°C.

[0030] As the polyol component (a1), for example, low molecular weight polyols such as ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, neopentyl glycol, 1,6-hexane glycol, 2,5-hexanediol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, tricyclodecane dimethanol, 1,4-cyclohexane dimethanol, etc. These low molecular weight polyols can be used alone or in combination of two or more.

[0031] As the polyol component (a1), a high molecular weight polyol can be used, for example, polycarbonate polyol (a1-1), polyether polyol (a1-2), polyester polyol (a1-3), polyether ester polyol (a1-4), etc. These high molecular weight polyols can be used alone or in combination of two or more.

[0032] From the viewpoints of the glass adhesion and chipping resistance of the coating film to be formed, it is preferable that the polyol component (a1) contains a polycarbonate polyol (a1-1).

[0033] The polycarbonate polyol (a1-1) is a compound obtained by polycondensation reaction of a known polyol component with a carbonylating agent by a conventional method. Examples of the polyol component include a diol component and a polyhydric alcohol component such as a trihydric or higher alcohol.

[0034] Examples of the diol component include linear diols such as 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol; 2-methyl-1,3-propanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 2-ethyl-1,6-hexanediol, 2,2-diethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3- Examples of the diol components include branched diols such as propanediol, 2-methyl-1,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, and 2-ethyl-1,3-hexanediol; alicyclic diols such as 1,3-cyclohexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; aromatic diols such as p-xylenediol and p-tetrachloroxylenediol; and ether diols such as diethylene glycol and dipropylene glycol. These diol components can be used alone or in combination of two or more.

[0035] From the viewpoint of glass adhesion and hardness of the coating film to be formed, the diol component preferably contains an alicyclic diol having a cycloalkylene group, and more preferably contains an alicyclic diol having a cycloalkylene group having 6 or more carbon atoms.

[0036] Specific examples of the alicyclic diol having a cycloalkylene group include 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol. Specific examples of the alicyclic diol having a cycloalkylene group having 6 or more carbon atoms include 1,4-cyclohexanediol and 1,4-cyclohexanedimethanol.

[0037] Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, a dimer of trimethylolpropane, pentaerythritol, etc. These trihydric or higher alcohols can be used alone or in combination of two or more kinds.

[0038] The carbonylating agent may be any known one. Specific examples include alkylene carbonate, dialkyl carbonate, diallyl carbonate, phosgene, etc., and these may be used alone or in combination of two or more. Among these, preferred examples include ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, diphenyl carbonate, etc.

[0039] The number average molecular weight of the polycarbonate polyol (a1-1) is preferably within a range of 500 to 10,000, more preferably within a range of 600 to 5,000, and particularly preferably within a range of 700 to 4,000, from the viewpoints of manufacturability and glass adhesion of the coating film formed.

[0040] From the viewpoints of image sharpness and chipping resistance of the coating film to be formed, it is preferable that the polyol component contains a polyether polyol (a1-2).

[0041] The polyether polyol (a1-2) may be an alkylene oxide adduct of the low molecular weight polyol, a ring-opening (co)polymer of an alkylene oxide or a cyclic ether (such as tetrahydrofuran), etc. Specific examples include polyethylene glycol, polypropylene glycol, a (block or random) copolymer of ethylene glycol-propylene glycol, polytetramethylene glycol, polyhexamethylene glycol, polyoctamethylene glycol, etc.

[0042] Among them, as the polyether polyol (a1-2), polyethylene glycol, polypropylene glycol, and polytetramethylene glycol can be preferably used. The number average molecular weight of the polyether polyol (a1-2) is preferably within the range of 500 to 10,000, more preferably within the range of 1,000 to 5,000, and particularly preferably within the range of 1,600 to 4,000, from the viewpoints of manufacturability, image sharpness and chipping resistance of the coating film formed, etc.

[0043] The polyether polyol (a1-2) can be used either individually or in combination of two or more.

[0044] The polyester polyol (a1-3) may be one obtained by polycondensing a dicarboxylic acid (anhydride) such as adipic acid, succinic acid, sebacic acid, glutaric acid, maleic acid, fumaric acid, or phthalic acid with a low molecular weight polyol such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octamethylenediol, or neopentyl glycol under conditions of excess hydroxyl groups. Specific examples include ethylene glycol-adipic acid condensate, butanediol-adipic acid condensate, hexamethylene glycol-adipic acid condensate, ethylene glycol-propylene glycol-adipic acid condensate, and polylactone polyols obtained by ring-opening polymerization of lactone using glycol as an initiator. These polyester polyols (a1-3) may be used alone or in combination of two or more.

[0045] Examples of the polyether ester polyol (a1-4) include those obtained by adding an ether group-containing polyol (the polyether polyol (a1-2) or diethylene glycol, etc.) or a mixture of this with other glycols to a dicarboxylic acid (anhydride) such as those exemplified for the polyester polyol (a1-3) above, and reacting with an alkylene oxide, such as polytetramethylene glycol-adipic acid condensate. These polyether ester polyols (a1-4) may be used alone or in combination of two or more.

[0046] Polyisocyanate component (a2) Examples of the polyisocyanate component (a2) include alicyclic diisocyanates, aromatic diisocyanates, aliphatic diisocyanates, and polyisocyanates having three or more isocyanate groups in one molecule. Examples of the alicyclic diisocyanate include isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, trans-1,4-cyclohexyl diisocyanate, and norbornene diisocyanate.

[0047] Examples of the aromatic diisocyanate include tolylene diisocyanate, diphenylmethane-4,4'-diisocyanate, p-phenylene diisocyanate, xylylene diisocyanate, 1,5-naphthylene diisocyanate, 3,3'-dimethyldiphenyl-4,4'-diisocyanate, dianisidine diisocyanate, and tetramethylxylylene diisocyanate.

[0048] Examples of the aliphatic diisocyanate include 1,6-hexamethylene diisocyanate, 2,2,4 and / or 2,4,4-trimethylhexamethylene diisocyanate, and lysine diisocyanate.

[0049] Examples of the polyisocyanate having three or more isocyanate groups in one molecule include isocyanurate trimer, biuret trimer, and trimethylolpropane adduct of the above-mentioned diisocyanates; and tri- or higher functional polyisocyanates such as triphenylmethane triisocyanate, 1-methylbenzene-2,4,6-triisocyanate, and dimethyltriphenylmethane tetraisocyanate. These isocyanate compounds may be used in the form of modified products such as carbodiimide-modified, isocyanurate-modified, and biuret-modified.

[0050] The above polyisocyanates may be used in the form of blocked isocyanates blocked with a blocking agent.

[0051] Compounds having both active hydrogen groups and ion-forming groups Examples of the compound having both an active hydrogen group and an ion-forming group include a compound having two or more hydroxyl groups and one or more carboxyl groups in one molecule, a compound having two or more hydroxyl groups and one or more sulfonic acid groups in one molecule, and a compound having two or more amino groups and one or more carboxyl groups in one molecule. These may be used alone or in combination of two or more kinds.

[0052] Among them, as the compound having both the active hydrogen group and the ion-forming group, a compound having two or more hydroxyl groups and one or more carboxyl groups in one molecule, and a compound having two or more hydroxyl groups and one or more sulfonic acid groups in one molecule can be preferably used. In the present invention, the compound having two or more hydroxyl groups and one or more carboxyl groups in one molecule, and the compound having two or more hydroxyl groups and one or more sulfonic acid groups in one molecule, which has two or more hydroxyl groups and an ion-forming group, are included in the polyol component (a1).

[0053] Examples of the compound having two or more hydroxyl groups and one or more carboxyl groups in one molecule include alkanol carboxylic acid compounds such as dimethylolpropionic acid, dimethylolacetic acid, dimethylolbutanoic acid, dimethylolheptanoic acid, dimethylolnonanoic acid, 1-carboxy-1,5-pentylenediamine, dihydroxybenzoic acid, and 3,5-diaminobenzoic acid, and half ester compounds of polyoxypropylenetriol with maleic anhydride and / or phthalic anhydride.

[0054] Examples of the compound having two or more hydroxyl groups and one or more sulfonic acid groups in one molecule include 2-sulfonic acid-1,4-butanediol, 5-sulfonic acid-di-β-hydroxyethyl isophthalate, and N,N-bis(2-hydroxyethyl)aminoethylsulfonic acid.

[0055] As the compound having both the above-mentioned active hydrogen group and the ion-forming group, from the viewpoint of the flexibility of the coating film to be formed, it is particularly preferable to use a compound having two or more hydroxyl groups and one or more carboxyl groups in the molecule.

[0056] From the viewpoint of water dispersion stability and the like, the urethane resin particles (A) preferably contain the above-mentioned compound having both an active hydrogen group and an ion-forming group.

[0057] When the compound having both an active hydrogen group and an ion-forming group is used, the amount used is, from the viewpoints of aqueous dispersion stability and the water resistance of the coating film formed, preferably within the range of 1 to 10 mass %, more preferably within the range of 1 to 7 mass %, and particularly preferably within the range of 1 to 5 mass %, based on the total amount of the compounds constituting the urethane resin particles (A).

[0058] The urethane resin particles (A) are usually synthesized as a dispersion in an aqueous solvent, and the form of the urethane resin particles (A) is not particularly limited as long as they are dispersed in an aqueous solvent. Here, the aqueous solvent refers to a solvent containing water as a main component (for example, a solvent in which 70 to 100 mass % of the solvent is water).

[0059] The method for producing the urethane resin particles (A) is not particularly limited, and can be any method known in the art. For example, the method for producing the urethane resin particles (A) includes a method in which a polyol component (a1) and a polyisocyanate component (a2) are reacted in an organic solvent to form a urethane, or a compound having both an active hydrogen group and an ion-forming group is further added to form a urethane to synthesize a prepolymer, and the obtained prepolymer is emulsified, and further chain extension reaction and desolvation are carried out as necessary.

[0060] In the urethane reaction of the polyol component (a1) and the polyisocyanate component (a1), a catalyst can be used as necessary.

[0061] Examples of the catalyst include bismuth carboxylate compounds such as bismuth tris(2-ethylhexanoate)(III); organotin compounds such as dibutyltin dilaurate, dibutyltin dioctoate, and stannous octoate; and tertiary amine compounds such as triethylamine and triethylenediamine.

[0062] Among these, bismuth-based catalysts are preferred from the standpoint of relatively low toxicity, environmental adaptability, and the like.

[0063] The urethane reaction is preferably carried out at a temperature of 50 to 120°C.

[0064] In this manner, a prepolymer for the urethane resin particles (A) can be obtained.

[0065] The number average molecular weight of the prepolymer is preferably within the range of 2,000 to 10,000, more preferably within the range of 3,000 to 8,000, and particularly preferably within the range of 4,000 to 7,000, from the viewpoints of the storage stability of the resulting aqueous coating composition and the glass adhesion of the coating film formed.

[0066] In the synthesis of the prepolymer, an organic solvent that is inactive to isocyanates and does not interfere with the urethane reaction can be used, and examples of such organic solvents include aromatic hydrocarbon solvents such as toluene and xylene, ester solvents such as ethyl acetate and butyl acetate, and ketone solvents such as acetone and methyl ethyl ketone. Among these, ketone solvents and ester solvents are preferably used from the viewpoint of water dispersion stability, etc.

[0067] If necessary, a neutralizing agent for the ion-forming groups and deionized water can be added to the above urethane prepolymer to disperse (emulsify) it in water, and if necessary, a chain extension reaction and desolvation can be further carried out to obtain an aqueous dispersion of urethane resin particles (A).

[0068] The neutralizing agent is not particularly limited as long as it can neutralize the ion-forming group, and examples of basic compounds for neutralization include organic amines such as ammonia, diethylamine, ethylethanolamine, diethanolamine, triethanolamine, monoethanolamine, monopropanolamine, isopropanolamine, ethylaminoethylamine, hydroxyethylamine, triethylamine, tributylamine, dimethylethanolamine, diethylenetriamine, N-methylmorpholine, and N-ethylmorpholine; or alkali metal hydroxides such as sodium hydroxide and potassium hydroxide. These neutralizing agents can be used alone or in combination of two or more.

[0069] As the neutralizing agent, from the viewpoint of the glass adhesion of the coating film formed, particularly the glass adhesion of the coating film formed when the aqueous coating composition of the present invention is cured at a relatively low temperature, N-methylmorpholine and / or N-ethylmorpholine are preferred, and N-methylmorpholine is more preferred.

[0070] These neutralizing agents are preferably used in an amount such that the final pH of the aqueous dispersion of the urethane resin particles (A) is about 6.0 to 9.0.

[0071] When the neutralizing agent is added, the amount of the neutralizing agent added is preferably 0.1 to 1.5 equivalents, and more preferably 0.3 to 1.2 equivalents, relative to the acid group such as a carboxyl group.

[0072] In order to improve the water dispersion stability of the urethane resin particles (A), an emulsifier such as a surfactant may be used.

[0073] As a means for obtaining an aqueous dispersion, dispersion using a normal stirrer is possible, but in order to obtain an aqueous dispersion having a finer particle size and a uniform size, a homomixer, homogenizer, disperser, line mixer, etc. can be used.

[0074] When carrying out a chain extension reaction (high molecular weight) of a urethane prepolymer, a chain extender other than water may be added as necessary to react the urethane prepolymer with the chain extender. As the chain extender, a known chain extender having active hydrogen may be used. Specifically, for example, diamine compounds such as ethylenediamine, hexamethylenediamine, cyclohexanediamine, cyclohexylmethanediamine, and isophoronediamine, triamine compounds such as diethylenetriamine, and hydrazine may be mentioned.

[0075] From the viewpoint of improving the degree of chain extension, trifunctional or higher amine compounds, such as triamine compounds, e.g., diethylenetriamine, can be preferably used. From the viewpoint of flexibility of the resulting coating film, diamine compounds, e.g., ethylenediamine, can be preferably used.

[0076] Furthermore, for the purpose of introducing a reactive functional group, a compound having one or more amines and one or more hydroxyl groups in one molecule, such as hydroxyethylaminoethylamine, can also be suitably used.

[0077] From the viewpoint of manufacturability, the content ratio of the polyol component (a1) and the polyisocyanate component (a2) in the urethane resin particles (A) is preferably within a range of 1 / 1.01 to 1 / 3.0, more preferably 1 / 1.05 to 1 / 2.0, in terms of the molar ratio of active hydrogen groups in the polyol component (a1) to isocyanate groups in the polyisocyanate component (a2).

[0078] As the emulsifier, well-known anionic surfactants, nonionic surfactants, cationic surfactants, amphoteric surfactants, polymeric surfactants, reactive surfactants, etc., which are used in urethane resin emulsions, can be used, and among these, anionic emulsifiers and nonionic emulsifiers can be preferably used. As the anionic emulsifier, for example, sodium salts and ammonium salts of alkylsulfonic acid, alkylbenzenesulfonic acid, alkylphosphoric acid, etc. can be mentioned. In addition, as the nonionic emulsifier, for example, polyoxyethylene oleyl ether, polyoxyethylene stearyl ether, polyoxyethylene lauryl ether, polyoxyethylene tridecyl ether, polyoxyethylene phenyl ether, polyoxyethylene nonyl phenyl ether, polyoxyethylene octyl phenyl ether, polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene monooleate, sorbitan monolaurate, sorbitan monostearate, sorbitan monostearate, sorbitan trioleate, polyoxyethylene sorbitan monolaurate, etc. can be mentioned. Also usable are polyoxyalkylene group-containing anionic emulsifiers having an anionic group and a polyoxyalkylene group such as a polyoxyethylene group or a polyoxypropylene group in one molecule, and reactive anionic emulsifiers having the anionic group and a polymerizable unsaturated group in one molecule.

[0079] The average particle diameter of the urethane resin particles (A) can be adjusted to a desired average particle diameter by adjusting particle size control factors such as the composition of raw materials (polyisocyanate component, polyol component, amine component, etc.), the type and amount of emulsifier, the charge ratio of emulsifier, the type and amount of neutralizing agent, etc.

[0080] The number average molecular weight of the urethane resin particles (A) is preferably 10,000 or more, more preferably 50,000 or more, and particularly preferably 100,000 or more, from the viewpoints of the storage stability of the resulting aqueous coating composition and the glass adhesion of the coating film formed.

[0081] From the viewpoints of the storage stability of the resulting aqueous coating composition and the image sharpness of the coating film formed, the average particle size of the urethane resin particles (A) is preferably within the range of 10 to 5,000 nm, more preferably within the range of 10 to 1,000 nm, particularly preferably within the range of 20 to 500 nm, and even more particularly preferably within the range of 50 to 300 nm.

[0082] In this specification, the average particle size of the urethane resin particles (A) is a value measured using a particle size distribution measuring device by dynamic light scattering after dilution with deionized water in a conventional manner at 20° C. As the particle size distribution measuring device by dynamic light scattering, for example, “ELSZ-2000” (product name, manufactured by Otsuka Electronics Co., Ltd.) can be used.

[0083] From the viewpoints of aqueous dispersion stability and the water resistance of the coating film formed, the urethane resin particles (A) preferably have an acid value in the range of 5 to 40 mgKOH / g, more preferably in the range of 5 to 30 mgKOH / g, and particularly preferably in the range of 10 to 30 mgKOH / g.

[0084] From the viewpoint of the water resistance of the coating film to be formed, the urethane resin particles (A) preferably have a hydroxyl value in the range of 0 to 100 mgKOH / g, more preferably in the range of 0 to 50 mgKOH / g, and particularly preferably in the range of 0 to 10 mgKOH / g.

[0085] The solid content concentration in the aqueous dispersion of the urethane resin particles (A) is preferably within the range of 20 to 50% by mass, more preferably within the range of 30 to 50% by mass. When the solid content concentration is 50% by mass or less, emulsification is facilitated, and the aqueous dispersion can be easily obtained. When the solid content concentration is 20% by mass or more, the amount of the solvent component is reduced, and the solid content of the aqueous coating composition can be increased.

[0086] In this specification, the term "solid content" refers to non-volatile components such as resins, curing agents, and pigments remaining after drying for 1 hour at 110° C. The solid content can be determined, for example, by weighing a sample into a heat-resistant container such as an aluminum foil cup, spreading the sample on the bottom surface of the container, drying for 1 hour at 110° C., and weighing the mass of the components remaining after drying.

[0087] In addition, in this specification, "solid content concentration" means the mass ratio of the solid content in the composition. Therefore, the solid content concentration of the composition can be calculated by, for example, weighing the composition into a heat-resistant container such as an aluminum foil cup, spreading the composition on the bottom of the container, drying at 110°C for 1 hour, weighing the mass of the components remaining in the composition after drying, and calculating the mass ratio of the components remaining after drying to the total mass of the composition before drying.

[0088] The content of the urethane resin particles (A) in the aqueous coating composition of the present invention is preferably 1 to 50 mass%, more preferably 5 to 45 mass%, and particularly preferably 10 to 40 mass%, based on the resin solid content in the aqueous coating composition, from the viewpoint of the glass adhesion and chipping resistance of the coating film formed. The resin solid content includes the solid content of the crosslinking agent (C) having reactivity with the reactive group-containing resin (B).

[0089] From the viewpoints of glass adhesion, image clarity, chipping resistance, and the like of the coating film to be formed, the urethane resin particles (A) are preferably urethane resin particles (A') having a core-shell structure.

[0090] Urethane resin particles having a core-shell structure (A') The urethane resin particles (A') having a core-shell structure are usually synthesized as a dispersion in an aqueous solvent, and the form of the urethane resin particles is not particularly limited as long as they are dispersed in an aqueous solvent, but it is preferable that the particles are dispersed in water as particles having a structure in which the urethane resin (A'-II) constituting the shell part is located around the urethane resin (A'-I) constituting the core part as a dispersion stabilizer. In other words, it is preferable that the particles are dispersed in an aqueous solvent in a form having a core-shell structure in which the urethane resin (A'-II) constituting the shell part is on the outside and the urethane resin (A'-I) constituting the core part is on the inside. It is considered that the particles actually have almost such a particle form.

[0091] Here, the aqueous solvent refers to a solvent containing water as a main component (for example, a solvent in which water accounts for 70 to 100% by mass).

[0092] The core-shell structure specifically refers to a structure in which components of different resin compositions exist within the same particle, and the central portion (core) and the outer shell portion (shell) are made of different resin compositions.

[0093] The core-shell structure is generally a layer structure in which the core part is completely covered by the shell part, but there may be cases in which the shell part is insufficient to form a layer structure depending on the mass ratio of the core part to the shell part, other conditions, etc. In such cases, the above-mentioned complete layer structure is not necessary, and a structure in which the core part is partially covered by the shell part may be used.

[0094] As a method for producing urethane resin particles (A') having a core-shell structure, any conventionally known method for producing urethane resin particles can be used as long as it can produce a form having a core-shell structure. However, from the viewpoint of production stability (dispersion stability of the obtained resin particles), it is preferable to produce the particles by the following method (consisting of steps 1 to 3 below). 1. First, a urethane resin (A'-II) that constitutes the shell portion having a hydroxyl group terminal and containing a hydrophilic group is synthesized. 2. Next, the raw materials for the urethane resin (A'-I) that constitutes the core part are added to synthesize an isocyanate-terminated prepolymer in which the urethane resin (A'-I) that constitutes the core part is grafted to the urethane resin (A'-II) that constitutes the shell part. 3. The resulting prepolymer is emulsified, and if necessary, a chain extension reaction and desolvation are carried out to obtain urethane resin particles (A') having a core-shell structure.

[0095] Therefore, the urethane resin particles (A') having the above-mentioned core-shell structure can be obtained, for example, by a production method including a step of reacting a monomer mixture containing a polyol component (a'1-II) of the urethane resin constituting the shell portion and a polyisocyanate component (a'2-II) of the urethane resin constituting the shell portion to obtain a urethane resin (A'-II) constituting the shell portion, and a step of reacting a monomer mixture containing a polyol component (a'1-I) of the urethane resin constituting the core portion and a polyisocyanate component (a'2-I) of the urethane resin constituting the core portion in the presence of the urethane resin (A'-II) constituting the shell portion to synthesize a urethane resin (A'-I) of the urethane resin constituting the core portion.

[0096] The urethane resin particles (A') having a core-shell structure will be described in more detail below, along with the production method thereof. However, the urethane resin particles (A') having a core-shell structure are not limited to those obtained by the production method described below.

[0097] Synthesis of urethane resin (A'-II) that constitutes the shell The urethane resin (A'-II) constituting the shell portion constitutes the shell portion of the urethane resin particle (A') having a core-shell structure, and can be synthesized using a polyol component (a'1-II) of the urethane resin constituting the shell portion, a polyisocyanate component (a'2-II) of the urethane resin constituting the shell portion, and, if necessary, a compound having both an active hydrogen group and an ion-forming group as a water-dispersible group-imparting component.

[0098] As the polyol component (a'1-II) of the urethane resin constituting the shell portion, the above-mentioned polyol component (a1) can be used, and these can be used alone or in combination of two or more kinds.

[0099] In particular, from the viewpoint of the glass adhesion and chipping resistance of the coating film formed, it is preferred that the polyol component (a'1-II) of the urethane resin constituting the shell portion contains at least one of the polycarbonate polyols (a1-1).

[0100] The polycarbonate polyol (a1-1) is a compound obtained by a conventional method, by polycondensation reaction of a known polyol component with a carbonylating agent. From the viewpoint of glass adhesion and hardness of the coating film to be formed, the polyol component preferably contains an alicyclic diol having a cycloalkylene group, and more preferably contains an alicyclic diol having a cycloalkylene group having 6 or more carbon atoms.

[0101] Specific examples of the alicyclic diol having a cycloalkylene group include 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol. Specific examples of the alicyclic diol having a cycloalkylene group having 6 or more carbon atoms include 1,4-cyclohexanediol and 1,4-cyclohexanedimethanol.

[0102] For this reason, from the viewpoints of the glass adhesion, chipping resistance, hardness, etc. of the coating film formed, it is preferable that the polyol component (a'1-II) of the urethane resin constituting the above-mentioned shell portion contains at least one polycarbonate polyol having a cycloalkylene group, and it is even more preferable that it contains a polycarbonate polyol having a cycloalkylene group having 6 or more carbon atoms.

[0103] When the polyol component (a'1-II) of the urethane resin constituting the shell portion contains the polycarbonate polyol (a1-1), the number average molecular weight of the polycarbonate polyol (a1-1) is preferably within the range of 500 to 10,000, more preferably within the range of 600 to 5,000, and even more preferably within the range of 700 to 4,000, from the viewpoint of manufacturability, etc.

[0104] As the polyisocyanate component (a'2-II) of the urethane resin constituting the shell portion, the above-mentioned polyisocyanate component (a2) can be used, and these can be used alone or in combination of two or more kinds.

[0105] As the polyisocyanate component (a'2-II) of the urethane resin constituting the shell portion, from the viewpoint of the yellowing resistance of the coating film formed, a polyisocyanate compound having a saturated aliphatic structure and / or a polyisocyanate compound having a saturated alicyclic structure can be suitably used. Specific examples of the polyisocyanate compound having a saturated aliphatic structure include hexamethylene diisocyanate (HMDI), and specific examples of the polyisocyanate compound having a saturated alicyclic structure include isophorone diisocyanate (IPDI), 4,4'-dicyclohexylmethane diisocyanate (hydrogenated MDI), and the like.

[0106] As the compound having both an active hydrogen group and an ion-forming group, for example, the compound having both an active hydrogen group and an ion-forming group exemplified in the urethane resin particles (A) can be used. Here, the compound having both two or more hydroxyl groups and an ion-forming group is included in the polyol component (a'1-II) of the urethane resin constituting the shell portion.

[0107] From the viewpoint of water dispersion stability and the like, the urethane resin (A'-II) constituting the shell preferably contains the above-mentioned compound having both an active hydrogen group and an ion-forming group.

[0108] As the compound having both the above-mentioned active hydrogen group and the ion-forming group, from the viewpoint of the flexibility of the coating film to be formed, a compound having two or more hydroxyl groups and one or more carboxyl groups in the molecule can be preferably used.

[0109] When the compound having both the above-mentioned active hydrogen group and an ion-forming group is used, the amount used is, from the viewpoints of aqueous dispersion stability and the water resistance of the coating film formed, preferably within the range of 2 to 40 mass %, more preferably within the range of 3 to 30 mass %, and particularly preferably within the range of 5 to 20 mass %, relative to the total amount of the compounds constituting the urethane resin (A'-II) constituting the shell portion.

[0110] When a compound containing a carboxyl group or a sulfonic acid group is used as a compound having both an active hydrogen group and an ion-forming group, a neutralizing agent for forming a salt and making the compound hydrophilic can be used, such as an amine compound such as trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, triethylenediamine, dimethylaminoethanol, N-methylmorpholine, or N-ethylmorpholine, or an alkali metal compound such as sodium hydroxide or potassium hydroxide. These neutralizing agents can also be used alone or in combination of two or more.

[0111] As the neutralizing agent, from the viewpoint of the glass adhesion of the coating film formed, particularly the glass adhesion of the coating film formed when the aqueous coating composition of the present invention is cured at a relatively low temperature, N-methylmorpholine and / or N-ethylmorpholine are preferred, and N-methylmorpholine is more preferred. Here, the heating temperature in the case of curing at the relatively low temperature is preferably within the range of 60 to 110°C, more preferably within the range of 65 to 100°C, and even more preferably within the range of 70 to 90°C.

[0112] The neutralization rate of the carboxyl group or sulfonic acid group can usually be set to 50 to 100 mol %.

[0113] The urethane resin (A'-II) constituting the shell portion is preferably synthesized under conditions of an excess of hydroxyl groups so that hydroxyl groups remain in the grafting process of the urethane resin (A'-I) constituting the core portion described later, from the viewpoint of improving the grafting efficiency.

[0114] From the viewpoint of manufacturability, etc., the content ratio of the polyol component (a'1-II) of the urethane resin constituting the shell portion and the polyisocyanate component (a'2-II) of the urethane resin constituting the shell portion in the urethane resin (A'-II) constituting the shell portion is preferably within the range of 1.01 / 1 to 3.0 / 1, and more preferably within the range of 1.05 / 1 to 2.0 / 1, in terms of the molar ratio of active hydrogen groups in the polyol component (a'1-II) of the urethane resin constituting the shell portion to isocyanate groups in the polyisocyanate component (a'2-II) of the urethane resin constituting the shell portion.

[0115] In the urethane reaction between the polyol component (a'1-II) of the urethane resin constituting the shell portion and the polyisocyanate component (a'2-II) of the urethane resin constituting the shell portion, a catalyst can be used as necessary.

[0116] Examples of the catalyst include bismuth carboxylate compounds such as bismuth tris(2-ethylhexanoate)(III); organotin compounds such as dibutyltin dilaurate, dibutyltin dioctoate, and stannous octoate; and tertiary amine compounds such as triethylamine and triethylenediamine.

[0117] Among these, bismuth-based catalysts are preferred from the standpoint of relatively low toxicity, environmental adaptability, and the like.

[0118] The urethane reaction is preferably carried out at a temperature of 50 to 120°C.

[0119] In the synthesis of the urethane resin (A'-II) constituting the shell part, the organic solvent can be an organic solvent that is inactive to isocyanate and does not interfere with the urethane reaction. Examples of such organic solvents include aromatic hydrocarbon solvents such as toluene and xylene, ester solvents such as ethyl acetate and butyl acetate, and ketone solvents such as acetone and methyl ethyl ketone. Among them, ketone solvents and ester solvents can be preferably used from the viewpoint of water dispersion stability.

[0120] In this manner, the urethane resin (A'-II) constituting the shell portion can be obtained.

[0121] Synthesis of prepolymer (grafting of urethane resin (A'-I) that constitutes the core part) The urethane resin particles (A') having a core-shell structure are preferably urethane resin particles having a core-shell structure obtained by synthesizing the urethane resin (A'-I) constituting the core portion in the presence of the urethane resin (A'-II) constituting the shell portion (i.e., synthesizing the urethane resin (A'-II) unit followed by the urethane resin (A'-I) unit), and grafting the urethane resin (A'-I) constituting the core portion to the urethane resin (A'-II) constituting the shell portion, thereby synthesizing a prepolymer in two steps, and dispersing the prepolymer in an aqueous medium (further undergoing a chain extension reaction if necessary).

[0122] The urethane resin (A'-I) constituting the core portion constitutes the core portion of the urethane resin particle (A') having a core-shell structure, and can be synthesized, for example, using a polyol component (a'1-I) of the urethane resin constituting the core portion and a polyisocyanate component (a'2-I) of the urethane resin constituting the core portion.

[0123] As the polyol component (a'1-I) of the urethane resin constituting the core part, the above-mentioned polyol component (a1) can be used, and these can be used alone or in combination of two or more kinds.

[0124] In particular, from the viewpoint of the image sharpness and chipping resistance of the coating film formed, it is preferred that the polyol component (a'1-I) of the urethane resin constituting the core portion contains at least one of the polyether polyols (a1-2).

[0125] From the viewpoints of image sharpness and chipping resistance of the coating film to be formed, it is preferable that the polyether polyol (a1-2) contains polytetramethylene glycol.

[0126] When the polyol component (a'1-I) of the urethane resin constituting the core portion contains the polyether polyol (a1-2), the number average molecular weight of the polyether polyol (a1-2) is preferably within the range of 500 to 10,000, more preferably within the range of 1,000 to 5,000, and particularly preferably within the range of 1,600 to 4,000, from the viewpoints of manufacturability and the sharpness of the coating film formed.

[0127] As the polyisocyanate component (a'2-I) of the urethane resin constituting the core part, the above-mentioned polyisocyanate component (a2) can be used, and these can be used alone or in combination of two or more kinds.

[0128] The urethane resin (A'-I) constituting the core portion is preferably synthesized under conditions of an excess of isocyanate groups so that isocyanate groups remain, from the viewpoint of making the final prepolymer to be isocyanate-terminated.

[0129] From the standpoint of manufacturability, the content ratio of the polyol component (a'1-I) of the urethane resin constituting the core portion and the polyisocyanate component (a'2-I) of the urethane resin constituting the core portion in the urethane resin (A'-I) constituting the core portion, expressed as a molar ratio of active hydrogen groups in the polyol component (a'1-I) of the urethane resin constituting the core portion to isocyanate groups in the polyisocyanate component (a'2-I) of the urethane resin constituting the core portion, is preferably within the range of 1 / 1.01 to 1 / 3.0, and more preferably within the range of 1 / 1.05 to 1 / 2.5.

[0130] In the urethane reaction between the polyol component (a'1-I) of the urethane resin constituting the core portion and the polyisocyanate component (a'2-I) of the urethane resin constituting the core portion, a catalyst can be used as necessary.

[0131] Examples of the catalyst include bismuth carboxylate compounds such as bismuth tris(2-ethylhexanoate)(III); organotin compounds such as dibutyltin dilaurate, dibutyltin dioctoate, and stannous octoate; and tertiary amine compounds such as triethylamine and triethylenediamine.

[0132] Among these, bismuth-based catalysts are preferred from the viewpoints of their relatively low toxicity and environmental adaptability.

[0133] The urethane reaction is preferably carried out at a temperature of 50 to 120°C.

[0134] In the synthesis of the prepolymer (grafting of the urethane resin (A'-I) constituting the core portion), an organic solvent that is inactive with isocyanate and does not interfere with the urethane reaction can be used, and examples of such organic solvents include aromatic hydrocarbon solvents such as toluene and xylene, ester solvents such as ethyl acetate and butyl acetate, and ketone solvents such as acetone and methyl ethyl ketone. Among these, ketone solvents and ester solvents can be preferably used from the viewpoint of water dispersion stability, etc.

[0135] Furthermore, the isocyanate groups of the prepolymer may be partially or entirely blocked with a blocking agent to form blocked isocyanate groups, if necessary.

[0136] In this manner, a prepolymer having a structure in which the urethane resin (A'-I) constituting the core portion and the urethane resin (A'-II) constituting the shell portion are grafted can be produced.

[0137] From the viewpoints of aqueous dispersion stability and the water resistance of the coating film formed, the acid value of the prepolymer is preferably within the range of 5 to 40 mgKOH / g, more preferably within the range of 5 to 30 mgKOH / g, and particularly preferably within the range of 10 to 30 mgKOH / g.

[0138] From the viewpoints of production stability and the image sharpness and water resistance of the coating film formed, the hydroxyl value of the prepolymer is preferably within the range of 0 to 100 mgKOH / g, more preferably within the range of 1.0 to 50 mgKOH / g, and particularly preferably within the range of 1.0 to 30 mgKOH / g.

[0139] The number average molecular weight of the prepolymer is preferably within a range of 2,000 to 50,000, more preferably within a range of 2,000 to 30,000, and particularly preferably within a range of 3,000 to 15,000, from the viewpoint of manufacturability and the like. Synthesis of urethane resin particles (A') having a core-shell structure If necessary, a neutralizing agent for the ion-forming groups and deionized water are added to the above prepolymer to carry out aqueous dispersion (emulsification), and if necessary, a chain extension reaction and desolvation are further carried out to obtain an aqueous dispersion of urethane resin particles (A') having a core-shell structure.

[0140] The neutralizing agent is not particularly limited as long as it can neutralize the ion-forming group, and examples of the basic compound for neutralization include the neutralizing agents exemplified in the neutralizing agent for the urethane resin particles (A). These neutralizing agents can be used alone or in combination of two or more.

[0141] Among the above neutralizing agents, N-methylmorpholine and / or N-ethylmorpholine are preferred, and N-methylmorpholine is more preferred, from the viewpoint of the glass adhesion of the coating film formed, particularly when the aqueous coating composition of the present invention is cured at a relatively low temperature. Here, the heating temperature when curing at the above relatively low temperature is preferably within the range of 60 to 110°C, more preferably within the range of 65 to 100°C, and even more preferably within the range of 70 to 90°C.

[0142] It is desirable to use these neutralizing agents in an amount such that the final pH of the aqueous dispersion of the urethane resin particles (A') having a core-shell structure is about 6.0 to 9.0.

[0143] When the neutralizing agent is added, the amount of the neutralizing agent added is preferably within the range of 0.1 to 1.5 equivalents, and more preferably within the range of 0.3 to 1.2 equivalents, relative to the acid group such as a carboxyl group.

[0144] As a means for obtaining an aqueous dispersion, dispersion using a normal stirrer is possible, but in order to obtain an aqueous dispersion having a finer particle size and a uniform size, a homomixer, homogenizer, disperser, line mixer, etc. can be used.

[0145] When carrying out the chain extension reaction (high molecular weight) of the prepolymer, a chain extender other than water may be added as necessary to react the urethane prepolymer with the chain extender. As the chain extender, a known chain extender having active hydrogen may be used. Specifically, for example, diamine compounds such as ethylenediamine, hexamethylenediamine, cyclohexanediamine, cyclohexylmethanediamine, and isophoronediamine, triamine compounds such as diethylenetriamine, and hydrazine may be mentioned.

[0146] From the viewpoint of improving the degree of chain extension, trifunctional or higher amine compounds, such as triamine compounds, e.g., diethylenetriamine, can be preferably used. From the viewpoint of flexibility of the coating film to be formed, diamine compounds, e.g., ethylenediamine, can be preferably used.

[0147] Furthermore, for the purpose of introducing a reactive functional group, a compound having one or more amines and one or more hydroxyl groups in one molecule, such as hydroxyethylaminoethylamine, can also be suitably used.

[0148] In the urethane resin particles (A') having a core-shell structure, the mass ratio (a'1-I) / (a'1-II) of the polyol component (a'1-I) of the urethane resin constituting the core portion and the polyol component (a'1-II) of the urethane resin constituting the shell portion is preferably within the range of 60 / 40 to 20 / 80, more preferably within the range of 50 / 50 to 20 / 80, and particularly preferably within the range of 40 / 60 to 20 / 80, from the viewpoints of glass adhesion, image clarity, chipping resistance, etc.

[0149] The number average molecular weight of the urethane resin particles (A') having a core-shell structure is preferably 2000 or more, more preferably 5000 or more, and particularly preferably 10000 or more, from the viewpoints of water dispersion stability and manufacturability.

[0150] From the viewpoints of aqueous dispersion stability and storage stability, the average particle size of the urethane resin particles (A') having a core-shell structure is preferably within the range of 10 to 5000 nm, more preferably within the range of 10 to 1000 nm, particularly preferably within the range of 20 to 500 nm, and even more particularly preferably within the range of 50 to 300 nm.

[0151] From the viewpoints of aqueous dispersion stability and the water resistance of the coating film formed, the urethane resin particles (A') having a core-shell structure preferably have an acid value in the range of 5 to 40 mgKOH / g, more preferably in the range of 5 to 30 mgKOH / g, and particularly preferably in the range of 10 to 30 mgKOH / g.

[0152] From the viewpoint of the water resistance of the coating film formed, the urethane resin particles (A') having a core-shell structure preferably have a hydroxyl value in the range of 0 to 100 mgKOH / g, more preferably in the range of 0 to 50 mgKOH / g, and particularly preferably in the range of 0 to 10 mgKOH / g.

[0153] The solid content concentration in the aqueous dispersion of the urethane resin particles (A') having a core-shell structure is preferably in the range of 20 to 50% by mass, more preferably in the range of 30 to 50% by mass. When the solid content concentration is 50% by mass or less, emulsification is easy and the aqueous dispersion can be easily obtained. When the solid content concentration is 20% by mass or more, the solvent component is reduced, so that the solid content concentration of the aqueous coating composition can be increased.

[0154] The content of the urethane resin particles (A') having a core-shell structure is preferably within the range of 1 to 50 mass%, more preferably 5 to 45 mass%, and particularly preferably 10 to 40 mass%, based on the resin solid content in the aqueous coating composition, from the viewpoints of the storage stability of the resulting aqueous coating composition and the image sharpness of the coating film formed.

[0155] Reactive group-containing resin (B) The reactive group-containing resin (B) is a resin other than the urethane resin particles (A), and the type of the reactive group-containing resin (B) is not particularly limited as long as it is a resin containing a reactive group, and examples thereof include acrylic resin, polyester resin, acrylic-modified polyester resin, urethane resin, urethane-modified polyester resin, epoxy resin, etc. Among them, from the viewpoint of glass adhesion, smoothness, chipping resistance, etc. of the coating film to be formed, it is preferable that the reactive group-containing resin (B) contains at least one resin selected from acrylic resin, polyester resin, and acrylic-modified polyester resin, and it is preferable that it contains acrylic resin and / or polyester resin.

[0156] The reactive group refers to a functional group having reactivity capable of crosslinking. Examples of the reactive group include hydroxyl, carboxyl, epoxy, carbonyl, N-methylol alkyl ether, isocyanate, amino, alkoxysilyl, carbodiimide, and hydrazide groups. In particular, from the viewpoint of glass adhesion, smoothness, and chipping resistance of the coating film to be formed, it is preferable that the reactive group-containing resin (B) has at least one of the reactive groups, hydroxyl and / or carboxyl, and more preferably has a hydroxyl. That is, from the viewpoint of glass adhesion, smoothness, and chipping resistance of the coating film to be formed, it is preferable that the reactive group-containing resin (B) contains a hydroxyl-containing resin (B').

[0157] When the reactive group-containing resin (B) has a hydroxyl group, the hydroxyl value is preferably within the range of 1 to 200 mgKOH / g, more preferably within the range of 2 to 180 mgKOH / g, and even more preferably within the range of 5 to 170 mgKOH / g. When the reactive group-containing resin (B) has an acid group such as a carboxyl group, the acid value is preferably within the range of 1 to 200 mgKOH / g, more preferably within the range of 2 to 150 mgKOH / g, and even more preferably within the range of 5 to 120 mgKOH / g.

[0158] The content of the reactive group-containing resin (B) in the aqueous coating composition of the present invention is preferably 20 to 70 mass %, more preferably 25 to 65 mass %, and particularly preferably 30 to 60 mass %, based on the resin solids content in the aqueous coating composition, from the viewpoints of glass adhesion and chipping resistance of the coating film to be formed.

[0159] [Hydroxyl-containing resin (B')] The hydroxyl-containing resin (B') is a resin having at least one hydroxyl group in one molecule.

[0160] Examples of the hydroxyl-containing resin (B') include hydroxyl-containing polyester resins, hydroxyl-containing acrylic resins, hydroxyl-containing acrylic-modified polyester resins, hydroxyl-containing polyether resins, hydroxyl-containing polycarbonate resins, hydroxyl-containing epoxy resins, and hydroxyl-containing alkyd resins. These can be used alone or in combination of two or more. However, in the present invention, the hydroxyl-containing resins corresponding to the urethane resin particles (A) are not included in the hydroxyl-containing resin (B').

[0161] In addition, the hydroxyl group-containing resin (B') preferably has an ion-forming group from the viewpoint of dispersion stability in water. Examples of the ion-forming group include a carboxyl group and a sulfonic acid group. When the reactive group-containing resin (B) has the ion-forming group, an amine compound such as trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, triethylenediamine, dimethylaminoethanol, N-methylmorpholine, and N-ethylmorpholine, and an alkali metal compound such as sodium hydroxide and potassium hydroxide can be used as a neutralizing agent to form a salt and make the resin hydrophilic. These neutralizing agents can also be used alone or in combination of two or more.

[0162] As the neutralizing agent, from the viewpoint of the glass adhesion of the coating film formed, particularly the glass adhesion of the coating film formed when the aqueous coating composition of the present invention is cured at a relatively low temperature, N-methylmorpholine and / or N-ethylmorpholine are preferred, and N-methylmorpholine is more preferred. Here, the heating temperature in the case of curing at the relatively low temperature is preferably within the range of 60 to 110°C, more preferably within the range of 65 to 100°C, and even more preferably within the range of 70 to 90°C.

[0163] When the aqueous coating composition of the present invention contains the above-mentioned hydroxyl-containing resin (B'), the content of the hydroxyl-containing resin (B') is, from the viewpoints of glass adhesion and chipping resistance of the coating film formed, preferably 20 to 70 mass %, more preferably 25 to 65 mass %, and particularly preferably 30 to 60 mass %, based on the resin solids content in the aqueous coating composition.

[0164] From the viewpoints of image sharpness and chipping resistance of the coating film formed, the hydroxyl-containing resin (B') preferably contains a hydroxyl-containing polyester resin (B'1).

[0165] From the viewpoints of the glass adhesion and chipping resistance of the coating film to be formed, it is preferable that the hydroxyl-containing resin (B') contains a hydroxyl-containing acrylic resin (B'2).

[0166] Hydroxyl-containing polyester resin (B'1) The hydroxyl-containing polyester resin (B'1) can be obtained, for example, by using a polyol having two or more hydroxyl groups as the alcohol component and a polycarboxylic acid having two or more carboxyl groups as the acid component, and condensing the alcohol component and the acid component.

[0167] As the polyol, a polyhydric alcohol having two or more hydroxyl groups in one molecule can be suitably used. Examples of the polyhydric alcohol include ethylene glycol, propylene glycol, diethylene glycol, trimethylene glycol, tetraethylene glycol, triethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 2,3-butanediol, 1,2-butanediol, 2-methyl-1,3-propanediol, 3-methyl-1,2-butanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,2-pentanediol, 1,5-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 2,3-dimethyltrimethylene glycol, tetramethylene glycol, 3-methyl-4,3-pentanediol, 3-methyl-1,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,6-hexanediol, 1,5-hexanediol, 1,4-hexanediol, 2,5-hexanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, tricyclohexane Examples of the polylactone diols include dihydric alcohols such as rodecanedimethanol, hydroxypivalic acid neopentyl glycol ester, hydrogenated bisphenol A, hydrogenated bisphenol F, and dimethylolpropionic acid; polylactone diols obtained by adding lactone compounds such as ε-caprolactone to these dihydric alcohols; ester diol compounds such as bis(hydroxyethyl)terephthalate; polyether diol compounds such as alkylene oxide adducts of bisphenol A, polyethylene glycol, polypropylene glycol, and polybutylene glycol; trihydric or higher alcohols such as glycerin, trimethylolethane, trimethylolpropane, diglycerin, triglycerin, 1,2,6-hexanetriol, pentaerythritol, dipentaerythritol, tris(2-hydroxyethyl)isocyanuric acid, sorbitol, and mannitol; polylactone polyol compounds obtained by adding lactone compounds such as ε-caprolactone to these trihydric or higher alcohols; and fatty acid esters of glycerin.

[0168] In addition, alcohol components other than the above polyols can also be used. Examples of such alcohol components include, but are not limited to, monoalcohols such as methanol, ethanol, propyl alcohol, butyl alcohol, stearyl alcohol, and 2-phenoxyethanol; and alcohol compounds obtained by reacting monoepoxy compounds such as propylene oxide, butylene oxide, and "Cardura E10" (trade name, manufactured by HEXION, glycidyl ester of synthetic highly branched saturated fatty acid) with acids.

[0169] The polycarboxylic acid may be a compound that is commonly used in the production of polyester resins, such as an aliphatic polybasic acid, an alicyclic polybasic acid, or an aromatic polybasic acid.

[0170] The above-mentioned aliphatic polybasic acid is generally an aliphatic compound having two or more carboxyl groups in one molecule, an acid anhydride of the aliphatic compound, and an esterification product of the aliphatic compound. Examples of the aliphatic polybasic acid include aliphatic polybasic carboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecane diacid, dodecane diacid, brassylic acid, octadecanedioic acid, citric acid, and butanetetracarboxylic acid; anhydrides of the aliphatic polybasic carboxylic acids; and lower alkyl esters of the aliphatic polybasic carboxylic acids having 1 to 6 carbon atoms, preferably 1 to 4 carbon atoms. The above-mentioned aliphatic polybasic acids can be used alone or in combination of two or more kinds.

[0171] The alicyclic polybasic acid is generally a compound having one or more alicyclic structures and two or more carboxyl groups in one molecule, an acid anhydride of the compound, and an esterification product of the compound. The alicyclic structure can be mainly a 4- to 6-membered ring structure. Examples of the alicyclic polybasic acid include alicyclic polycarboxylic acids such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 4-cyclohexene-1,2-dicarboxylic acid, 3-methyl-1,2-cyclohexanedicarboxylic acid, 4-methyl-1,2-cyclohexanedicarboxylic acid, 1,2,4-cyclohexanetricarboxylic acid, and 1,3,5-cyclohexanetricarboxylic acid; anhydrides of the alicyclic polybasic acid; and lower alkyl esters of the alicyclic polybasic carboxylic acids having 1 to 6 carbon atoms, preferably 1 to 4 carbon atoms. The alicyclic polybasic acids can be used alone or in combination of two or more kinds.

[0172] The aromatic polybasic acid is generally an aromatic compound having two or more carboxyl groups in one molecule, an acid anhydride of the aromatic compound, and an esterification product of the aromatic compound. Examples of the aromatic polybasic acid include aromatic polycarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, trimellitic acid, and pyromellitic acid; anhydrides of the aromatic polybasic acid; and lower alkyl esters of the aromatic polybasic carboxylic acids having 1 to 6 carbon atoms, preferably 1 to 4 carbon atoms. The aromatic polybasic acids can be used alone or in combination of two or more kinds. As the aromatic polybasic acid, it is preferable to use phthalic acid, phthalic anhydride, isophthalic acid, trimellitic acid, and trimellitic anhydride, and it is more preferable to use trimellitic anhydride.

[0173] In addition, acid components other than the above-mentioned aliphatic polybasic acids, alicyclic polybasic acids, and aromatic polybasic acids can also be used. Such acid components are not particularly limited, and examples thereof include fatty acids such as coconut oil fatty acid, cottonseed oil fatty acid, hempseed oil fatty acid, rice bran oil fatty acid, fish oil fatty acid, tall oil fatty acid, soybean oil fatty acid, linseed oil fatty acid, tung oil fatty acid, rapeseed oil fatty acid, castor oil fatty acid, dehydrated castor oil fatty acid, and safflower oil fatty acid; monocarboxylic acids such as lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, benzoic acid, p-tert-butylbenzoic acid, cyclohexanoic acid, and 10-phenyloctadecanoic acid; and hydroxycarboxylic acids such as lactic acid, 3-hydroxybutanoic acid, and 3-hydroxy-4-ethoxybenzoic acid. These acid components can be used alone or in combination of two or more.

[0174] The method for producing the hydroxyl-containing polyester resin (B'1) is not particularly limited and can be carried out according to a conventional method. For example, the hydroxyl-containing polyester resin (B'1) can be produced by heating the alcohol component and the acid component in a nitrogen stream at about 150 to 250°C for about 5 to 10 hours to carry out an esterification reaction or an ester exchange reaction between the alcohol component and the acid component.

[0175] When the alcohol component and the acid component are subjected to an esterification reaction or an ester exchange reaction, these components may be added to a reaction vessel at once, or one or both may be added in several portions. Alternatively, a hydroxyl-containing polyester resin may be first synthesized, and then the resulting hydroxyl-containing polyester resin may be reacted with an acid anhydride to half-esterify the resulting hydroxyl-containing polyester resin to obtain a carboxyl- and hydroxyl-containing polyester resin. Alternatively, a carboxyl-containing polyester resin may be first synthesized, and then the alcohol component may be added to produce the hydroxyl-containing polyester resin.

[0176] In the esterification or transesterification reaction, a catalyst known per se, such as dibutyltin oxide, antimony trioxide, zinc acetate, manganese acetate, cobalt acetate, calcium acetate, lead acetate, tetrabutyl titanate, or tetraisopropyl titanate, can be used as a catalyst for promoting the reaction.

[0177] The hydroxyl-containing polyester resin (B'1) may be modified with a fatty acid, a monoepoxy compound, a polyisocyanate compound, or the like during or after the production of the resin.

[0178] Examples of the fatty acids include coconut oil fatty acids, cottonseed oil fatty acids, hempseed oil fatty acids, rice bran oil fatty acids, fish oil fatty acids, tall oil fatty acids, soybean oil fatty acids, linseed oil fatty acids, tung oil fatty acids, rapeseed oil fatty acids, castor oil fatty acids, dehydrated castor oil fatty acids, safflower oil fatty acids, and the like. An example of the monoepoxy compound that can be suitably used is "Cardura E10P" (trade name, manufactured by HEXION, glycidyl ester of synthetic highly branched saturated fatty acid).

[0179] As the polyisocyanate compound, the polyisocyanates exemplified in the polyisocyanate component (a2) can be used. These can be used alone or in combination of two or more kinds.

[0180] The hydroxyl value of the hydroxyl-containing polyester resin (B'1) is preferably within the range of 1 to 200 mgKOH / g, more preferably within the range of 2 to 180 mgKOH / g, and particularly preferably within the range of 5 to 170 mgKOH / g, from the viewpoints of glass adhesion and chipping resistance of the coating film formed.

[0181] The number average molecular weight of the hydroxyl-containing polyester resin (B'1) is preferably within the range of 500 to 50,000, more preferably within the range of 1,000 to 30,000, and particularly preferably within the range of 1,200 to 10,000, from the viewpoints of chipping resistance and glass adhesion of the coating film formed.

[0182] The glass transition temperature (Tg) of the hydroxyl-containing polyester resin (B'1) is preferably within the range of -20°C to 50°C, more preferably within the range of -10°C to 40°C, and particularly preferably within the range of -5°C to -35°C, from the viewpoints of chipping resistance and glass adhesion of the coating film formed.

[0183] From the viewpoint of the stability of the aqueous coating composition, the above hydroxyl group-containing polyester resin (B'1) preferably contains a carboxyl group.

[0184] When the hydroxyl-containing polyester resin (B'1) has a carboxyl group, the acid value of the hydroxyl-containing polyester resin (B'1) is preferably within the range of 5 to 150 mg KOH / g, more preferably within the range of 10 to 140 mg KOH / g, and particularly preferably within the range of 15 to 120 mg KOH / g, from the viewpoint of the stability of the aqueous coating composition, etc.

[0185] When the aqueous coating composition of the present invention contains the above-mentioned hydroxyl-containing polyester resin (B'1), the content of the hydroxyl-containing polyester resin (B'1) is preferably 1 to 45 mass%, more preferably 5 to 40 mass%, and particularly preferably 10 to 35 mass%, based on the resin solids content in the aqueous coating composition, from the viewpoints of glass adhesion and chipping resistance of the coating film formed.

[0186] Hydroxyl-containing acrylic resin (B'2) The hydroxyl-containing acrylic resin (B'2) can usually be produced by copolymerizing a hydroxyl-containing polymerizable unsaturated monomer and another polymerizable unsaturated monomer copolymerizable with the hydroxyl-containing polymerizable unsaturated monomer by a method known per se, such as a solution polymerization method in an organic solvent or an emulsion polymerization method in an aqueous medium.

[0187] The emulsion polymerization can be carried out by a conventionally known method such as a seed polymerization method or a mini-emulsion polymerization method, for example, by emulsion polymerizing a polymerizable unsaturated monomer using a polymerization initiator in the presence of an emulsifier.

[0188] More specifically, the emulsion polymerization can be carried out by dissolving an emulsifier in an aqueous medium containing water or, if necessary, an organic solvent such as alcohol, and dropping a polymerizable unsaturated monomer and a polymerization initiator while heating and stirring. A polymerizable unsaturated monomer previously emulsified using an emulsifier and water can also be dropped in the same manner.

[0189] The hydroxyl group-containing polymerizable unsaturated monomer is a compound having at least one hydroxyl group and at least one polymerizable unsaturated group in one molecule, and examples thereof include monoesters of (meth)acrylic acid and dihydric alcohols having 2 to 8 carbon atoms, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; ε-caprolactone-modified products of these monoesters; N-hydroxymethyl (meth)acrylamide; allyl alcohol; and (meth)acrylates having a polyoxyethylene chain having a hydroxyl group at the molecular terminal.

[0190] However, in the present invention, a monomer corresponding to the polymerizable unsaturated monomer having an ultraviolet absorbing functional group (xvii) described later should be defined as another polymerizable unsaturated monomer copolymerizable with the hydroxyl group-containing polymerizable unsaturated monomer, and is excluded from the hydroxyl group-containing polymerizable unsaturated monomer. The above hydroxyl group-containing polymerizable unsaturated monomers can be used alone or in combination of two or more kinds.

[0191] In this specification, the polymerizable unsaturated group refers to an unsaturated group capable of radical polymerization. Examples of such polymerizable unsaturated groups include vinyl groups, (meth)acryloyl groups, (meth)acrylamide groups, vinyl ether groups, allyl groups, propenyl groups, isopropenyl groups, and maleimide groups.

[0192] In this specification, "(meth)acrylate" means acrylate or methacrylate, "(meth)acrylic acid" means acrylic acid or methacrylic acid, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylamide" means acrylamide or methacrylamide.

[0193] The other polymerizable unsaturated monomers copolymerizable with the hydroxyl-containing polymerizable unsaturated monomers can be appropriately selected and used according to the properties desired for the hydroxyl-containing acrylic resin. Specific examples of the other polymerizable unsaturated monomers copolymerizable with the hydroxyl-containing polymerizable unsaturated monomers include those listed in the following (i) to (xix). Each of these can be used alone or in combination of two or more. (i) Alkyl or cycloalkyl (meth)acrylates: for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, tricyclodecanyl (meth)acrylate, and the like. (ii) Polymerizable unsaturated monomers having an isobornyl group: for example, isobornyl (meth)acrylate. (iii) Polymerizable unsaturated monomers having an adamantyl group: for example, adamantyl (meth)acrylate. (iv) Polymerizable unsaturated monomers having a tricyclodecenyl group: for example, tricyclodecenyl (meth)acrylate. (v) Aromatic ring-containing polymerizable unsaturated monomers: for example, benzyl (meth)acrylate, styrene, α-methylstyrene, vinyltoluene, and the like. (vi) Polymerizable unsaturated monomers having an alkoxysilyl group: for example, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, γ-(meth)acryloyloxypropyltrimethoxysilane, γ-(meth)acryloyloxypropyltriethoxysilane, and the like. (vii) Polymerizable unsaturated monomers having a fluorinated alkyl group: for example, perfluoroalkyl (meth)acrylates such as perfluorobutylethyl (meth)acrylate and perfluorooctylethyl (meth)acrylate; fluoroolefins, and the like. (viii) Polymerizable unsaturated monomers having a photopolymerizable functional group such as a maleimide group. (ix) Vinyl compounds: for example, N-vinylpyrrolidone, ethylene, butadiene, chloroprene, vinyl propionate, vinyl acetate, etc. (x) Carboxyl group-containing polymerizable unsaturated monomers: for example, (meth)acrylic acid, maleic acid, crotonic acid, β-carboxyethyl acrylate, and the like. (xi) Nitrogen-containing polymerizable unsaturated monomers: for example, (meth)acrylonitrile, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, methylene bis(meth)acrylamide, ethylene bis(meth)acrylamide, 2-(methacryloyloxy)ethyltrimethylammonium chloride, and adducts of glycidyl (meth)acrylate with amines. (xii) Polymerizable unsaturated monomers having two or more polymerizable unsaturated groups in one molecule: for example, allyl(meth)acrylate, ethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, etc. (xiii) Epoxy group-containing polymerizable unsaturated monomers: for example, glycidyl (meth)acrylate, β-methylglycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 3,4-epoxycyclohexylethyl (meth)acrylate, 3,4-epoxycyclohexylpropyl (meth)acrylate, allyl glycidyl ether, and the like. (xiv) (meth)acrylates having a polyoxyethylene chain having an alkoxy group at the molecular terminal. (xv) Polymerizable unsaturated monomers having a sulfonic acid group: for example, 2-acrylamido-2-methylpropanesulfonic acid, 2-sulfoethyl (meth)acrylate, allylsulfonic acid, 4-styrenesulfonic acid, etc.; sodium salts and ammonium salts of these sulfonic acids. (xvi) Polymerizable unsaturated monomers having a phosphate group: acid phosphooxyethyl (meth)acrylate, acid phosphooxypropyl (meth)acrylate, acid phosphooxypoly(oxyethylene)glycol (meth)acrylate, acid phosphooxypoly(oxypropylene)glycol (meth)acrylate, and the like. (xvii) Polymerizable unsaturated monomers having an ultraviolet absorbing functional group: for example, 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, 2-hydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole, and the like. (xviii) Light-stable polymerizable unsaturated monomers: for example, 4-(meth)acryloyloxy-1,2,2,6,6-pentamethylpiperidine, 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-(meth)acryloylamino-2,2,6 ,6-tetramethylpiperidine, 1-(meth)acryloyl-4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 4-crotonoyloxy-2,2,6,6-tetramethylpiperidine, 4-crotonoylamino-2,2,6,6-tetramethylpiperidine, 1-crotonoyl-4-crotonoyloxy-2,2,6,6-tetramethylpiperidine, etc. (xix) Polymerizable unsaturated monomers having a carbonyl group: for example, acrolein, diacetone acrylamide, diacetone methacrylamide, acetoacetoxyethyl methacrylate, formyl styrene, vinyl alkyl ketones having 4 to 7 carbon atoms (for example, vinyl methyl ketone, vinyl ethyl ketone, vinyl butyl ketone), and the like.

[0194] The hydroxyl-containing acrylic resin (B'2) can also be used in combination with a so-called urethane-modified acrylic resin, which is obtained by subjecting some of the hydroxyl groups in the resin to a urethane reaction with a polyisocyanate compound to elongate and increase the molecular weight.

[0195] The content of the hydroxyl group-containing polymerizable unsaturated monomer is preferably within a range of 1 to 50 mass %, more preferably within a range of 2 to 40 mass %, and particularly preferably within a range of 3 to 30 mass %, based on the total amount of the hydroxyl group-containing polymerizable unsaturated monomer and other polymerizable unsaturated monomers copolymerizable with the hydroxyl group-containing polymerizable unsaturated monomer.

[0196] The hydroxyl value of the hydroxyl-containing acrylic resin (B'2) is preferably in the range of 1 to 200 mgKOH / g, more preferably in the range of 2 to 150 mgKOH / g, and particularly preferably in the range of 5 to 100 mgKOH / g, from the viewpoints of glass adhesion and chipping resistance of the coating film formed.

[0197] The acid value of the hydroxyl-containing acrylic resin (B'2) is preferably within the range of 1 to 200 mgKOH / g, more preferably within the range of 2 to 150 mgKOH / g, and particularly preferably within the range of 5 to 80 mgKOH / g, from the viewpoints of glass adhesion and water resistance of the coating film formed.

[0198] The weight average molecular weight of the hydroxyl-containing acrylic resin (B'2) is generally preferably within the range of 2,000 to 5,000,000, more preferably within the range of 4,000 to 1,000,000, and particularly preferably within the range of 8,000 to 500,000, from the viewpoints of glass adhesion and chipping resistance of the coating film formed.

[0199] In this specification, the number average molecular weight and the weight average molecular weight are values ​​obtained by converting the retention time (retention volume) measured using gel permeation chromatography (GPC) into the molecular weight of polystyrene based on the retention time (retention volume) of a standard polystyrene with a known molecular weight measured under the same conditions. Specifically, the gel permeation chromatography apparatus is "HLC-8120GPC" (trade name, manufactured by Tosoh Corporation), and four columns, "TSKgel G4000HXL", "TSKgel G3000HXL", "TSKgel G2500HXL" and "TSKgel G2000HXL" (trade names, all manufactured by Tosoh Corporation), are used, and a differential refractometer is used as a detector, and the measurements can be performed under the following conditions: mobile phase: tetrahydrofuran, measurement temperature: 40°C, flow rate: 1mL / min.

[0200] The emulsifier is preferably an anionic emulsifier or a nonionic emulsifier. Examples of the anionic emulsifier include sodium salts and ammonium salts of organic acids such as alkylsulfonic acid, alkylbenzenesulfonic acid, and alkylphosphoric acid, and examples of the nonionic emulsifier include polyoxyethylene oleyl ether, polyoxyethylene stearyl ether, polyoxyethylene lauryl ether, polyoxyethylene tridecyl ether, polyoxyethylene phenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene monooleate, sorbitan monolaurate, sorbitan monostearate, sorbitan trioleate, and polyoxyethylene sorbitan monolaurate.

[0201] Polyoxyalkylene group-containing anionic emulsifiers having an anionic group and a polyoxyalkylene group such as a polyoxyethylene group or a polyoxypropylene group in one molecule, or reactive anionic emulsifiers having the anionic group and a radically polymerizable unsaturated group in one molecule may be used, and among these, it is preferable to use reactive anionic emulsifiers.

[0202] Examples of the reactive anionic emulsifier include sodium salts and ammonium salts of sulfonic acid compounds having radically polymerizable unsaturated groups such as (meth)allyl groups, (meth)acryloyl groups, propenyl groups, and butenyl groups. Among them, ammonium salts of sulfonic acid compounds having radically polymerizable unsaturated groups are preferred because they provide excellent water resistance to the coating film formed. Examples of the ammonium salts of sulfonic acid compounds include commercially available products such as "Latemul S-180A" (trade name, manufactured by Kao Corporation).

[0203] Among the ammonium salts of sulfonic acid compounds having the above radical polymerizable unsaturated group, the ammonium salts of sulfonic acid compounds having radical polymerizable unsaturated group and polyoxyalkylene group are more preferred.As the ammonium salts of sulfonic acid compounds having the above radical polymerizable unsaturated group and polyoxyalkylene group, for example, commercially available products such as "Aqualon KH-10" (trade name, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and "SR-1025A" (trade name, manufactured by Asahi Denka Kogyo Co., Ltd.) can be mentioned.

[0204] The emulsifier is preferably used in an amount of 0.1 to 15 mass %, more preferably 0.5 to 10 mass %, and particularly preferably 1 to 5 mass %, based on the total amount of all monomers used.

[0205] The polymerization initiator may be either oil-soluble or water-soluble, and examples thereof include organic peroxides such as benzoyl peroxide, octanoyl peroxide, lauroyl peroxide, stearoyl peroxide, cumene hydroperoxide, tert-butyl peroxide, tert-butyl peroxy laurate, tert-butyl peroxy isopropyl carbonate, tert-butyl peroxy acetate, and diisopropylbenzene hydroperoxide; azobisisobutyronite; azo compounds such as azobis(2,4-dimethylvaleronitrile), azobis(2-methylpropiononitrile), azobis(2-methylbutyronitrile), 4,4'-azobis(4-cyanobutanoic acid), dimethylazobis(2-methylpropionate), azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], azobis{2-methyl-N-[2-(1-hydroxybutyl)]-propionamide}; and persulfates such as potassium persulfate, ammonium persulfate, sodium persulfate, etc. These can be used alone or in combination of two or more kinds.

[0206] Furthermore, the above polymerization initiator may be used in combination with a reducing agent such as sugar, sodium formaldehyde sulfoxylate, or an iron complex, if necessary, to form a redox polymerization system.

[0207] The polymerization initiator is preferably used in an amount of usually 0.1 to 5% by mass, particularly 0.2 to 3% by mass, based on the total mass of all monomers used. The method of adding the polymerization initiator is not particularly limited and can be appropriately selected depending on the type and amount. For example, the polymerization initiator may be previously contained in the monomer mixture or aqueous medium, or may be added all at once or dropwise during polymerization.

[0208] When the aqueous coating composition of the present invention contains the above-mentioned hydroxyl-containing acrylic resin particles (B'2), the content of the hydroxyl-containing acrylic resin particles (B'2) is, from the viewpoints of the glass adhesion and chipping resistance of the coating film formed, preferably 1 to 50 mass%, more preferably 5 to 45 mass%, and particularly preferably 10 to 40 mass%, based on the resin solids content in the aqueous coating composition.

[0209] The hydroxyl-containing acrylic resin (B'2) preferably contains hydroxyl-containing acrylic resin particles having a core-shell structure from the viewpoints of the water resistance, glass adhesion, and image clarity of the coating film formed. In particular, from the viewpoints of the glass adhesion and image clarity of the coating film formed when the aqueous coating composition of the present invention is cured at a relatively low temperature, the hydroxyl-containing acrylic resin (B'2) preferably contains hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer.

[0210] The gradient polymer layer of the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure containing the gradient polymer layer means a polymer layer having a layer structure in which the composition changes continuously (having a composition gradient).

[0211] More specifically, it means a polymer layer having a composition gradient in which the monomer (monomer mixture) composition changes continuously, for example, from monomer A (monomer mixture A) to monomer B (monomer mixture B).

[0212] The gradient polymer layer can generally be obtained by a known polymerization method called power feed polymerization. Specifically, for example, when two types of monomer A (monomer mixture A) and monomer B (monomer mixture B) are polymerized, the gradient polymer layer can be obtained by introducing monomer A (monomer mixture A) into a reaction vessel while dropping monomer B (monomer mixture B) into a vessel containing monomer A (monomer mixture A) and carrying out the polymerization reaction.

[0213] In the above power feed polymerization, a gradient polymer layer having a desired composition gradient can be obtained by adjusting the synthesis conditions (the timing of starting mixing of monomer A (monomer mixture A) and monomer B (monomer mixture B), the rate at which monomer B (monomer mixture B) is dropped into a vessel containing monomer A (monomer mixture A), and the rate at which monomer A (monomer mixture A) is introduced into a reaction vessel, etc.).

[0214] In addition, the "shell portion" of the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including the gradient polymer layer means the polymer layer present in the outermost layer of the resin particle, the "core portion" means the polymer layer in the inner layer of the resin particle excluding the shell portion, and "having a core-shell structure" means a structure having the core portion and shell portion.

[0215] The core-shell structure is generally a layer structure in which the core part is completely covered by the shell part, but the amount of monomer in the shell part may be insufficient to form a layer structure depending on the mass ratio of the core part to the shell part, etc. In such a case, the above-mentioned complete layer structure is not necessary, and a structure in which the core part is partially covered by the shell part may be used.

[0216] The hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer are acrylic resin particles consisting of a core portion which is a copolymer (I) having a polymerizable unsaturated monomer as a copolymerization component, a shell portion which is a copolymer (II) having a polymerizable unsaturated monomer as a copolymerization component, and a gradient polymer layer present between the core portion and the shell portion.

[0217] As the polymerizable unsaturated monomer, the hydroxyl group-containing polymerizable unsaturated monomer and another polymerizable unsaturated monomer copolymerizable with the hydroxyl group-containing polymerizable unsaturated monomer can be used in appropriate combination.

[0218] To produce the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure containing the gradient polymer layer, a mixture of polymerizable unsaturated monomers is first emulsion-polymerized to prepare an emulsion of the core copolymer (I).

[0219] The emulsion polymerization for preparing the emulsion of the core copolymer (I) can be carried out by a conventionally known method.For example, it can be carried out by emulsion polymerization of a polymerizable unsaturated monomer mixture using a polymerization initiator in the presence of an emulsifier.As the emulsifier and polymerization initiator, for example, the above-mentioned emulsifier and polymerization initiator can be used.

[0220] In order to obtain the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure containing the gradient polymer layer, a gradient polymer layer is subsequently formed. The gradient polymer layer can be formed by the power feed polymerization or the like described above.

[0221] To form the gradient polymer layer, a polymerizable unsaturated monomer mixture used in the emulsion polymerization of the core copolymer (I) and a polymerizable unsaturated monomer mixture used in the emulsion polymerization of the shell copolymer (II) can usually be used.

[0222] The hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure containing the gradient polymer layer can be obtained by further forming a shell copolymer (II).

[0223] The monomer mixture for forming the shell copolymer (II) may contain, as necessary, the polymerization initiator, chain transfer agent, reducing agent, emulsifier, and other components. The monomer mixture may be dropped as is, but it is preferable to drop the monomer mixture as a monomer emulsion obtained by dispersing the monomer mixture in an aqueous medium. In this case, the particle size of the monomer emulsion is not particularly limited.

[0224] An example of a method for polymerizing the monomer mixture for forming the shell copolymer (II) is to add the monomer mixture or an emulsion thereof, either dropwise in one go or dropwise slowly, to the emulsion of the core copolymer (I) and then heat to an appropriate temperature while stirring.

[0225] The ratio of the gradient polymer layer in the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer is preferably about 20 to 80 mass %, particularly preferably about 25 to 75 mass %, and even more particularly preferably about 30 to 70 mass %, based on the total amount of all copolymerization components of the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer, from the viewpoint of the water resistance of the resulting coating film, etc.

[0226] The hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer preferably have a hydroxyl value in the range of 1 to 150 mgKOH / g, more preferably in the range of 2 to 120 mgKOH / g, and even more preferably in the range of 5 to 100 mgKOH / g, from the viewpoints of the curability, chipping resistance, adhesion, and finished appearance of the resulting coating film.

[0227] The core portion of the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer preferably has a hydroxyl value in the range of 0 to 150 mgKOH / g, more preferably in the range of 5 to 120 mgKOH / g, and even more preferably in the range of 10 to 100 mgKOH / g, from the viewpoints of the water resistance and chipping resistance of the resulting coating film.

[0228] The shell portion of the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer preferably has a hydroxyl value in the range of 0 to 150 mgKOH / g, more preferably in the range of 2 to 120 mgKOH / g, and even more preferably in the range of 5 to 100 mgKOH / g, from the viewpoints of the water resistance and chipping resistance of the resulting coating film.

[0229] The hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer preferably have an acid value in the range of 1 to 80 mgKOH / g, more preferably in the range of 5 to 50 mgKOH / g, and even more preferably in the range of 5 to 30 mgKOH / g, from the viewpoints of the storage stability of the coating material and the water resistance of the resulting coating film.

[0230] The core portion of the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer preferably has an acid value in the range of 0 to 50 mgKOH / g, more preferably in the range of 0 to 30 mgKOH / g, and even more preferably in the range of 0 to 10 mgKOH / g, from the viewpoints of production stability and storage stability of the coating material.

[0231] The shell portion of the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer preferably has an acid value within the range of 1 to 100 mgKOH / g, more preferably within the range of 5 to 80 mgKOH / g, and even more preferably within the range of 10 to 50 mgKOH / g, from the viewpoints of the storage stability of the coating material and the water resistance of the resulting coating film.

[0232] The hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer preferably have a glass transition temperature of 20°C or higher, more preferably 30°C or higher, and even more preferably 30 to 100°C, from the viewpoints of the water resistance, hardness, chipping resistance, etc. of the resulting coating film.

[0233] The core portion of the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer preferably has a glass transition temperature within the range of -50 to 50°C, more preferably within the range of -30 to 50°C, and even more preferably within the range of 0 to 50°C, from the viewpoints of the water resistance, hardness, film-forming properties, chipping resistance, etc. of the resulting coating film.

[0234] The shell portion of the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer preferably has a glass transition temperature of 40°C or higher, more preferably 50°C or higher, and even more preferably within the range of 50 to 100°C, from the viewpoints of the hardness and water resistance of the resulting coating film.

[0235] In this specification, the glass transition temperature Tg of the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer is a value calculated by the following formula. 1 / Tg(K)=W1 / T1+W2 / T2+...Wn / Tn Tg(℃)=Tg(K)-273 In the formula, W1, W2, ...Wn are the mass fractions of each monomer, and T1, T2...Tn are the glass transition temperatures Tg (K) of the homopolymers of each monomer. The glass transition temperature of the homopolymer of each monomer is a value according to POLYMER HANDBOOK Fourth Edition, edited by J. Brandrup, Eh Immergut, and EA Grulke (1999). For the glass transition temperature of a monomer not described in the document, a homopolymer of the monomer is synthesized so as to have a weight-average molecular weight of about 50,000, and the glass transition temperature is measured by differential scanning calorimetry.

[0236] In the aqueous coating composition of the present invention, the content of the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including a gradient polymer layer is preferably within the range of 2 to 70 mass%, more preferably within the range of 5 to 50 mass%, and even more preferably within the range of 10 to 40 mass%, based on the resin solid content in the aqueous coating composition.

[0237] [Crosslinking agent (C)] The crosslinking agent (C) is not particularly limited. For example, a crosslinking agent having reactivity with the reactive group of the reactive group-containing resin (B) can be used.

[0238] Examples of the crosslinking agent (C) include known crosslinking agents, specifically, for example, amino resins, polyisocyanate compounds, blocked polyisocyanate compounds, polyhydrazide compounds, polysemicarbazide compounds, carbodiimide compounds, oxazoline group-containing compounds, epoxy compounds, polycarboxylic acids, etc. The crosslinking agents may be used alone or in combination of two or more kinds.

[0239] From the viewpoint of the glass adhesion and chipping resistance of the coating film to be formed, the crosslinking agent (C) preferably contains at least one crosslinking agent selected from an amino resin, a polyisocyanate compound, and a blocked polyisocyanate compound, more preferably contains an amino resin and / or a blocked polyisocyanate compound, and particularly preferably contains an amino resin and a blocked polyisocyanate compound.

[0240] Amino Resins As the amino resin, a partially methylolated amino resin or a completely methylolated amino resin obtained by the reaction of an amino component with an aldehyde component can be used. Examples of the amino component include melamine, urea, benzoguanamine, acetoguanamine, steroguanamine, spiroguanamine, and dicyandiamide. Examples of the aldehyde component include formaldehyde, paraformaldehyde, acetaldehyde, and benzaldehyde.

[0241] The methylolated amino resins may also be used in which the methylol groups have been partially or completely etherified with a suitable alcohol, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, 2-ethyl-1-butanol, 2-ethyl-1-hexanol, etc.

[0242] As the amino resin, a melamine resin is preferred. In particular, a methyl-etherified melamine resin in which the methylol groups of a partially or fully methylolated melamine resin are partially or completely etherified with methyl alcohol, a butyl-etherified melamine resin in which the methylol groups of a partially or fully methylolated melamine resin are partially or completely etherified with butyl alcohol, or a methyl-butyl mixed etherified melamine resin in which the methylol groups of a partially or fully methylolated melamine resin are partially or completely etherified with methyl alcohol and butyl alcohol are preferred, and a methyl-butyl mixed etherified melamine resin is more preferred.

[0243] The weight average molecular weight of the melamine resin is preferably within a range of 450 to 6,000, more preferably within a range of 500 to 4,000, and particularly preferably within a range of 550 to 3,000.

[0244] As the melamine resin, commercially available products can be used. Examples of the commercially available product names include "Cymel 202", "Cymel 203", "Cymel 211", "Cymel 238", "Cymel 251", "Cymel 254", "Cymel 303", "Cymel 325", "Cymel 327", "Cymel 350", "Cymel 370", "Cymel 385", "Cymel 1156", "Cymel 1158", and "Cymel 1130" (all manufactured by Allnex Japan Co., Ltd.); "U-Ban 20SE60" and "U-Ban 28-60" (all manufactured by Mitsui Chemicals, Inc.); and the like.

[0245] When the above-mentioned melamine resin is used as the crosslinking agent (C), a curing catalyst may be used as needed, such as a sulfonic acid such as paratoluenesulfonic acid, dodecylbenzenesulfonic acid, or dinonylnaphthalenesulfonic acid; a neutral salt of such a sulfonic acid with an amine; or a neutral salt of a phosphoric acid ester compound with an amine.

[0246] The amino resin can be used, for example, as a crosslinking agent for a resin containing a hydroxyl group.

[0247] Polyisocyanate Compounds The polyisocyanate compound is a compound having two or more isocyanate groups in one molecule.

[0248] The polyisocyanate compound includes, for example, aliphatic polyisocyanates, alicyclic polyisocyanates, araliphatic polyisocyanates, aromatic polyisocyanates, and derivatives of the polyisocyanates.

[0249] Examples of the aliphatic polyisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, dimer acid diisocyanate, methyl 2,6-diisocyanatohexanoate (common name: lysine diisocyanate), aliphatic diisocyanates such as 2-isocyanatoethyl 2,6-diisocyanatohexanoate, 1,6-diisocyanato-3-isocyanatomethylhexane, 1,4,8-triisocyanatooctane, 1,6,11-triisocyanatoundecane, 1,8-diisocyanato-4-isocyanatomethyloctane, 1,3,6-triisocyanatohexane, and 2,5,7-trimethyl-1,8-diisocyanato-5-isocyanatomethyloctane.

[0250] Examples of the alicyclic polyisocyanate include alicyclic diisocyanates such as 1,3-cyclopentene diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (common name: isophorone diisocyanate), methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 1,3- or 1,4-bis(isocyanatomethyl)cyclohexane (common name: hydrogenated xylylene diisocyanate) or a mixture thereof, and norbornane diisocyanate; 1,3,5-triisocyanatocyclohexane, 1,3,5-trimethylisocyanatocyclohexane, 2-(3-isocyanatopropyl)-2,5-di(isocyanatomethyl)-bicyclo(2.2.1)hepta, 2-(3-isocyanatopropyl)-2,6-di(isocyanatomethyl)-bicyclo(2.2.1)heptane, 3-(3-isocyanatopropyl)-2,5-di(isocyanatomethyl)-bicyclo(2.2.1)heptane, 5-(2-isocyanatoethyl)-2-isocyanatomethyl-3-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, 6-(2-isocyanatoethyl)-2-isocyanatoethyl alicyclic triisocyanates such as 2-isocyanatoethyl-3-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, 5-(2-isocyanatoethyl)-2-isocyanatomethyl-2-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, and 6-(2-isocyanatoethyl)-2-isocyanatomethyl-2-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane.

[0251] Examples of the aromatic aliphatic polyisocyanate include aromatic aliphatic diisocyanates such as 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene (common name: tetramethylxylylene diisocyanate) or a mixture thereof; and aromatic aliphatic triisocyanates such as 1,3,5-triisocyanatomethylbenzene.

[0252] Examples of the aromatic polyisocyanate include aromatic diisocyanates such as m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 2,4'- or 4,4'-diphenylmethane diisocyanate or a mixture thereof, 2,4- or 2,6-tolylene diisocyanate or a mixture thereof, 4,4'-toluidine diisocyanate, and 4,4'-diphenylether diisocyanate; aromatic triisocyanates such as triphenylmethane-4,4',4''-triisocyanate, 1,3,5-triisocyanatobenzene, and 2,4,6-triisocyanatotoluene; and aromatic tetraisocyanates such as 4,4'-diphenylmethane-2,2',5,5'-tetraisocyanate.

[0253] Examples of the derivatives of the polyisocyanate include dimers, trimers, biurets, allophanates, uretdione, uretoimine, isocyanurates, oxadiazinetriones, polymethylene polyphenyl polyisocyanates (crude MDI, polymeric MDI), crude TDI, and the like of the above-mentioned polyisocyanate compounds.

[0254] The polyisocyanates and derivatives thereof may be used alone or in combination of two or more thereof. Among these polyisocyanates, it is preferable to use aliphatic diisocyanates, alicyclic diisocyanates, and derivatives thereof alone or in combination of two or more thereof.

[0255] As the polyisocyanate compound, a prepolymer obtained by subjecting the above polyisocyanate or its derivative to a urethane reaction with a polyhydric alcohol, a low molecular weight polyester resin or water under conditions of an excess of isocyanate groups can also be used. When a polyisocyanate compound is used as the crosslinking agent (C), an organometallic compound, an acid compound, a base compound or the like can be used as a curing catalyst as necessary.

[0256] The polyisocyanate compound can be used, for example, as a crosslinking agent for a resin containing a hydroxyl group or an amino group.

[0257] Blocked polyisocyanate compounds The blocked polyisocyanate compound is a compound in which the isocyanate group of the polyisocyanate compound is blocked with a blocking agent.

[0258] Examples of the blocking agent include phenol-based agents such as phenol, cresol, xylenol, nitrophenol, ethylphenol, hydroxydiphenyl, butylphenol, isopropylphenol, nonylphenol, octylphenol, and methyl hydroxybenzoate; lactam-based agents such as ε-caprolactam, δ-valerolactam, γ-butyrolactam, and β-propiolactam; aliphatic alcohol-based agents such as methanol, ethanol, propyl alcohol, butyl alcohol, amyl alcohol, and lauryl alcohol; ether-based agents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol monomethyl ether, and methoxymethanol; benzyl alcohol, glycolic acid, methyl glycolate, ethyl glycolate, butyl glycolate, lactic acid, methyl lactate, ethyl lactate, butyl lactate, methylol urea, methylol melamine, diacetone alcohol, 2-hydroxyethyl acrylate ... Alcohol-based compounds such as diethyl methacrylate; oxime-based compounds such as formamide oxime, acetamide oxime, acetoxime, methyl ethyl ketoxime, diacetyl monooxime, benzophenone oxime, and cyclohexane oxime; active methylene-based compounds such as dimethyl malonate, diethyl malonate, ethyl acetoacetate, methyl acetoacetate, and acetylacetone; butyl mercaptan, tert-butyl mercaptan, hexyl mercaptan, tert-dodecyl mercaptan, 2-mercaptobenzothiazole, thiophenol, and methylthiophenone. mercaptans such as acetanilide, acetaniside, acetotoluide, acrylamide, methacrylamide, acetate amide, stearic acid amide, benzamide, and other acid amides; imides such as succinimide, phthalic acid amide, and maleic acid amide; amines such as diphenylamine, phenylnaphthylamine, xylidine, N-phenylxylidine, carbazole, aniline, naphthylamine, butylamine, dibutylamine, and butylphenylamine; imidazoles such as imidazole and 2-ethylimidazole;Examples of the azole compounds include urea compounds such as urea, thiourea, ethyleneurea, ethylenethiourea, and diphenylurea; carbamic acid ester compounds such as N-phenyl phenylcarbamate; imine compounds such as ethyleneimine and propyleneimine; sulfite compounds such as sodium bisulfite and potassium bisulfite; and azole compounds. Examples of the azole compounds include pyrazole compounds or pyrazole derivatives such as pyrazole, 3,5-dimethylpyrazole, 3-methylpyrazole, 4-benzyl-3,5-dimethylpyrazole, 4-nitro-3,5-dimethylpyrazole, 4-bromo-3,5-dimethylpyrazole, and 3-methyl-5-phenylpyrazole; imidazole compounds or imidazole derivatives such as imidazole, benzimidazole, 2-methylimidazole, 2-ethylimidazole, and 2-phenylimidazole; and imidazoline derivatives such as 2-methylimidazoline and 2-phenylimidazoline.

[0259] Among them, the blocking agent is preferably an oxime-based blocking agent, an active methylene-based blocking agent, pyrazole or a pyrazole derivative.

[0260] Furthermore, as the blocking agent, a hydroxycarboxylic acid having one or more hydroxyl groups and one or more carboxyl groups, such as hydroxypivalic acid and dimethylolpropionic acid, can also be used.

[0261] When the above-mentioned blocked polyisocyanate is used in the aqueous coating composition of the present invention, a blocked polyisocyanate compound in which the isocyanate groups are blocked with the above-mentioned hydroxycarboxylic acid and then the carboxyl groups of the hydroxycarboxylic acid are neutralized to impart water dispersibility can be preferably used.

[0262] From the viewpoint of the glass adhesion and image clarity of the coating film formed, particularly the glass adhesion and image clarity of the coating film formed when the aqueous coating composition of the present invention is cured at a relatively low temperature, it is preferable that the blocked polyisocyanate compound contains a structure derived from a spacer having at least two isocyanate-reactive functional groups.

[0263] The functional group is not particularly limited as long as it is a functional group that is reactive to an isocyanate group. Examples of the isocyanate-reactive functional group include a hydroxyl group, an amino group, a carboxyl group, and a thiol group, among which a hydroxyl group and an amino group are preferred, and a hydroxyl group is particularly preferred.

[0264] Therefore, the spacer is preferably a compound having at least two hydroxyl groups or a compound having at least two amino groups, and more preferably a compound having at least two hydroxyl groups.

[0265] Examples of the compound having at least two hydroxyl groups include, for example, low molecular weight compounds such as dihydric alcohols such as ethylene glycol, diethylene glycol, propylene glycol, butylene glycol, and hexamethylene glycol, and trihydric alcohols such as trimethylolpropane, glycerin, and pentaerythritol, and high molecular weight compounds such as polyether polyols, polyester polyols, acrylic polyols, and epoxy polyols. Among these, polyether polyols are preferred from the viewpoint of the water resistance and chipping resistance of the resulting coating film.

[0266] As the polyether polyol, the polyether polyols exemplified in the polyol component (a1) can be used. These can be used alone or in combination of two or more kinds.

[0267] Moreover, an example of the compound having at least two amino groups is polyetheramine.

[0268] The polyetheramine may be a commercially available product, such as "JEFFAMINE D-400", "JEFFAMINE D-2000", "JEFFAMINE D-4000", "JEFFAMINE ED-600", "JEFFAMINE ED-900", "JEFFAMINE ED-2003", "ELASTAMINE RT-1000", "JEFFAMINE T-403", "JEFFAMINE T-3000", or "JEFFAMINE T-5000" manufactured by HUNTSMAN.

[0269] The molecular weight of the spacer is preferably within the range of 500 to 6,000, more preferably within the range of 800 to 5,000, and even more preferably within the range of 1,500 to 3,500, from the viewpoints of the low-temperature curing properties of the aqueous coating composition of the present invention and the hardness, chipping resistance, and water resistance of the coating film formed.

[0270] The number of functional groups in the spacer is preferably 2 to 3, and more preferably 2, from the viewpoint of the storage stability of the aqueous coating composition of the present invention.

[0271] By reacting a part of the isocyanate groups in the polyisocyanate compound with a spacer, a polyisocyanate compound containing a structure derived from the spacer can be formed. In this case, from the viewpoint of the storage stability of the aqueous coating composition of the present invention, the hardness and water resistance of the coating film formed, and the manufacturing stability of the blocked polyisocyanate compound, the ratio of the polyisocyanate compound to the spacer is preferably in the range of 0.03 to 0.6 moles of active hydrogen per mole of isocyanate group in the polyisocyanate compound. By blocking the polyisocyanate compound containing a structure derived from the spacer, a blocked polyisocyanate compound containing a structure derived from the spacer can be formed.

[0272] From the viewpoint of the glass adhesion and image clarity of the coating film formed, particularly the glass adhesion and image clarity of the coating film formed when the aqueous coating composition of the present invention is cured at a relatively low temperature, the blocked polyisocyanate compound preferably contains a blocked polyisocyanate compound having a weight average molecular weight in the range of 20,000 to 200,000. Here, the heating temperature in the case of curing at a relatively low temperature is preferably in the range of 60 to 110°C, more preferably in the range of 65 to 100°C, and even more preferably in the range of 70 to 90°C.

[0273] When a polyisocyanate compound is used as the crosslinking agent (C), an organometallic compound, an acid compound, a base compound, etc. may be used as a curing catalyst, if necessary.

[0274] In the aqueous coating composition of the present invention, the content of the above-mentioned crosslinking agent (C) is preferably 5 to 55 mass %, more preferably 10 to 50 mass %, and particularly preferably 15 to 45 mass %, based on the resin solid content in the aqueous coating composition, from the viewpoints of glass adhesion and chipping resistance of the coating film to be formed.

[0275] [Other ingredients] The aqueous coating composition of the present invention may further contain, as necessary, resins other than the urethane resin particles (A), the reactive group-containing resin (B), and the crosslinking agent (C), pigments, organic solvents, curing catalysts, dispersants, anti-settling agents, defoamers, thickeners, UV absorbers, light stabilizers, surface conditioners, etc.

[0276] Examples of resins other than the urethane resin particles (A), reactive group-containing resin (B), and crosslinking agent (C) include polyurethane resins that have no reactive groups other than the urethane resin particles (A), acrylic resins that have no reactive groups, polyester resins that have no reactive groups, acrylic-modified polyester resins that have no reactive groups, acrylic-modified polyurethane resins that have no reactive groups, polyether resins that have no reactive groups, polycarbonate resins that have no reactive groups, epoxy resins that have no reactive groups, alkyd resins that have no reactive groups, and polyolefin resins that have no reactive groups.

[0277] Examples of the pigment include color pigments, extender pigments, luster pigments, etc. The pigments may be used alone or in combination of two or more kinds.

[0278] When the aqueous coating composition of the present invention contains the above-mentioned pigment, the amount of the pigment is preferably within the range of 1 to 200 parts by mass, more preferably within the range of 20 to 160 parts by mass, and particularly preferably within the range of 50 to 140 parts by mass, based on 100 parts by mass of the resin solids in the aqueous coating composition.

[0279] Examples of the color pigment include titanium oxide, zinc oxide, carbon black, molybdenum red, Prussian blue, cobalt blue, azo pigments, phthalocyanine pigments, quinacridone pigments, isoindoline pigments, threne pigments, perylene pigments, dioxazine pigments, and diketopyrrolopyrrole pigments. Among these, titanium oxide and carbon black are preferably used.

[0280] When the aqueous coating composition contains the above-mentioned coloring pigment, the amount of the coloring pigment is preferably within the range of 1 to 180 parts by mass, more preferably within the range of 5 to 150 parts by mass, and particularly preferably within the range of 15 to 130 parts by mass, based on 100 parts by mass of the resin solids in the aqueous coating composition.

[0281] Examples of the extender pigment include barium sulfate, talc, clay, kaolin, barium carbonate, calcium carbonate, silica, alumina white, etc. As the extender pigment, barium sulfate and talc are preferably used from the viewpoints of paint stability, smoothness, etc.

[0282] When the aqueous coating composition contains the above-mentioned extender pigment, the amount of the extender pigment is preferably within the range of 1 to 180 parts by mass, more preferably within the range of 5 to 140 parts by mass, and particularly preferably within the range of 10 to 120 parts by mass, based on 100 parts by mass of the resin solids in the aqueous coating composition.

[0283] Examples of the luster pigment include aluminum (including vapor-deposited aluminum), copper, zinc, brass, nickel, glass flakes, aluminum oxide, mica, aluminum oxide coated with titanium oxide and / or iron oxide, and mica coated with titanium oxide and / or iron oxide. Among these, the above are preferable. Aluminum pigments include non-leafing aluminum pigments, and aluminum pigments that are used in combination with leafing aluminum pigments, and any of these can be used.

[0284] The above-mentioned bright pigment is preferably in the form of a scale, and the bright pigment suitably has a longitudinal dimension in the range of 1 to 100 μm, particularly in the range of 5 to 40 μm, and a thickness in the range of 0.001 to 5 μm, particularly in the range of 0.01 to 2 μm.

[0285] When the aqueous coating composition contains the above-mentioned luster pigment, the amount of the luster pigment is preferably within the range of 0.1 to 100 parts by mass, more preferably within the range of 1 to 50 parts by mass, and particularly preferably within the range of 3 to 25 parts by mass, based on 100 parts by mass of the resin solids in the aqueous coating composition.

[0286] Examples of the organic solvent include ketone-based solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ester-based solvents such as ethyl acetate, butyl acetate, methyl benzoate, ethyl ethoxypropionate, ethyl propionate, and methyl propionate; alcohol-based solvents such as isopropanol, n-butanol, isobutanol, and 2-ethylhexanol; ether-based solvents such as tetrahydrofuran, dioxane, and dimethoxyethane; glycol ether-based solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate; aromatic hydrocarbon-based solvents, and aliphatic hydrocarbon-based solvents.

[0287] When used, the aqueous coating composition can be diluted by adding water and / or an organic solvent, etc., as necessary, and adjusted to an appropriate viscosity before coating.

[0288] The appropriate viscosity varies depending on the coating composition, but when adjusted using a Ford cup viscometer No. 4, for example, it can usually be about 20 to 70 seconds at 20°C, and a viscosity of about 25 to 50 seconds is preferable.

[0289] In the above, the coating solids concentration of the aqueous coating composition is usually about 5 to 70 mass %, and preferably about 10 to 60 mass %.

[0290] The aqueous coating composition may be either a one-component coating or a multi-component coating, but a one-component coating is preferred from the viewpoints of excellent productivity due to the absence of a coating mixing step and simplification of maintenance of coating machinery.

[0291] The aqueous coating composition can be applied to a substrate by a method known per se, such as air spray coating, airless spray coating, rotary atomization coating, curtain coat coating, etc., and electrostatic application may be performed during coating. Among these, air spray coating and rotary atomization coating are preferred. Furthermore, such coating methods can be performed once or several times until a desired film thickness is obtained.

[0292] The coating amount of the aqueous coating composition is usually such that the dry film thickness is 5 to 40 μm, preferably 7 to 35 μm, and more preferably 10 to 30 μm.

[0293] The pencil hardness of a coating film having a dry thickness of 15 μm obtained by applying the aqueous coating composition of the present invention is preferably HB or higher, and more preferably F or higher, from the viewpoint of glass adhesion of the coating film formed.

[0294] The above pencil hardness is, for example, the hardness symbol of the hardest pencil that does not break the coating film when a sample is applied to a glass plate so that the film thickness based on the dried coating film is 15 μm and dried under conditions of 80° C. for 30 minutes to form a dried coating film, and then the core of a pencil is placed at an angle of about 45° to the coating film surface and, while pressing the core against the coating film surface firmly enough not to break, the pencil is moved forward at a uniform speed for 10 mm.

[0295] [Coating film formation method] The aqueous coating composition of the present invention is capable of forming a coating film that exhibits excellent coating film performance, such as high hardness and water resistance, even when cured at a relatively low temperature. Therefore, the aqueous coating composition of the present invention can be suitably used in a coating film formation method in which the aqueous coating composition of the present invention is applied to a substrate to form an uncured colored coating film, and then the uncured colored coating film is heated at a temperature in the range of 60 to 110°C, preferably in the range of 65 to 100°C, and more preferably in the range of 70 to 90°C to cure it.

[0296] A preferred embodiment of the coating film forming method is the following method (I).

[0297] Method(I) Step (I-1): A step of applying the aqueous coating composition of the present invention onto a substrate to form an uncured colored coating film; and A method for forming a coating film, comprising: step (I-2): heating the uncured colored coating film formed in step (I-1) at a temperature in the range of 60 to 110°C to cure it.

[0298] Examples of the substrates include outer and inner panels of automobile bodies such as passenger cars, trucks, motorcycles, and buses, automobile parts, and outer panels of household electrical appliances such as mobile phones and audio equipment. Of these, the outer and inner panels of automobile bodies and automobile parts are preferred.

[0299] The material of these substrates is not particularly limited. For example, metal materials such as iron, aluminum, brass, copper, tinplate, stainless steel, zinc-plated steel, zinc alloy (Zn-Al, Zn-Ni, Zn-Fe, etc.)-plated steel; resins such as polyethylene resin, polypropylene resin, acrylonitrile-butadiene-styrene (ABS) resin, polyamide resin, acrylic resin, vinylidene chloride resin, polycarbonate resin, polyurethane resin, epoxy resin, and various plastic materials such as FRP; inorganic materials such as glass, cement, and concrete; wood; and fiber materials such as paper and cloth. Among these, metal materials and plastic materials are preferred.

[0300] The surfaces of the objects to which the coating film is applied may be metal surfaces such as the outer and inner panels of automobile bodies, automobile parts, household electrical appliances, and the metal substrates such as the steel plates that make up these items, which have been subjected to surface treatments such as phosphate treatment, chromate treatment, complex oxide treatment, etc.

[0301] A coating film may be further formed on the object, which may or may not have been surface-treated. For example, a substrate to be coated may be surface-treated as necessary, and an undercoat coating film may be formed thereon. For example, when the substrate to be coated is an automobile body, the undercoat coating film may be formed using a known undercoat paint that is normally used in the painting of automobile bodies.

[0302] In particular, the above-mentioned substrate is preferably a metal substrate, which may or may not have been surface-treated, on which an undercoat coating film is formed using an electrodeposition paint, preferably a cationic electrodeposition paint, and it is even more preferable that the undercoat coating film formed using the electrodeposition paint, preferably a cationic electrodeposition paint, is heat-cured.

[0303] [Multi-layer coating film formation method] The aqueous coating composition of the present invention can be suitably used for forming a multi-layer coating film consisting of a colored coating film, a base coat coating film and a clear coat coating film on a substrate such as an automobile body by the 3-coat 1-bake method. In this case, the coating film can be formed according to the following method II.

[0304] Method (II) Step (II-1): A step of applying a colored coating composition (X) to a substrate to form an uncured colored coating film; Step (II-2): (II-2) A step of applying a base coat paint composition (Y) onto the coating film formed by the uncured colored coating composition (X) to form an uncured base coat coating film; Step (II-3): A step of applying a clear coat paint composition (Z) onto the uncured base coat film to form an uncured clear coat film; and Step (II-4): A method for forming a multilayer coating film, comprising a step of heating the uncured colored coating film, the uncured base coat coating film and the uncured clear coat coating film to simultaneously cure them, wherein the colored coating composition (X) is the aqueous coating composition of the present invention.

[0305] Examples of the substrate include those exemplified in the substrate of the coating film forming method. Among them, the substrate is preferably an automobile body on which an undercoat coating film is formed. Among them, the substrate is preferably a metal substrate that may or may not be surface-treated, on which an undercoat coating film is formed by an electrodeposition paint, preferably a cationic electrodeposition paint, and more preferably the undercoat coating film formed by the electrodeposition paint, preferably a cationic electrodeposition paint, is heat-cured. As the base coat paint composition, a paint made of a base resin such as an acrylic resin, polyester resin, alkyd resin, urethane resin, or epoxy resin having a crosslinkable functional group such as a carboxyl group or a hydroxyl group, an amino resin such as a melamine resin or a urea resin, or a crosslinking agent such as a polyisocyanate compound that may be blocked, together with a pigment, a thickener, and other optional components can be used.

[0306] In particular, the base coat paint composition preferably contains a hydroxyl-containing resin as the base resin and a crosslinking agent having reactivity with hydroxyl groups as the crosslinking agent. The hydroxyl-containing resin may be the hydroxyl-containing resin described in the description of the hydroxyl-containing resin (B'). The crosslinking agent having reactivity with hydroxyl groups may be the crosslinking agent described in the description of the crosslinking agent (C).

[0307] The hydroxyl-containing resin preferably has an ion-forming group from the viewpoint of dispersion stability in water. Examples of the ion-forming group include carboxyl group and sulfonic acid group. When the hydroxyl-containing resin has the ion-forming group, an amine compound such as trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, triethylenediamine, dimethylaminoethanol, N-methylmorpholine, and N-ethylmorpholine, and an alkali metal compound such as sodium hydroxide and potassium hydroxide can be used as a neutralizing agent to form a salt and make it hydrophilic. These neutralizing agents can also be used alone or in combination of two or more.

[0308] As the neutralizing agent, from the viewpoints of the glass adhesion and image clarity of the multilayer coating film formed when the multilayer coating film is cured at a relatively low temperature in the above-mentioned Method II, N-methylmorpholine and / or N-ethylmorpholine is preferred, and N-methylmorpholine is more preferred.

[0309] In addition, from the viewpoint of the glass adhesion and image clarity of the multilayer coating film formed when the multilayer coating film is cured at a relatively low temperature in the above-mentioned method II, it is preferable that the above-mentioned hydroxyl-containing resin contains hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including the gradient polymer layer.

[0310] In addition, from the viewpoints of glass adhesion and image clarity of the multi-layer coating film formed when the multi-layer coating film is cured at a relatively low temperature in the above-mentioned method II, it is preferable that the crosslinking agent contains a blocked polyisocyanate compound having a weight average molecular weight in the range of 20,000 to 200,000.

[0311] Furthermore, in the case of curing at the above-mentioned relatively low temperature, the heating temperature is preferably within the range of 60 to 110°C, more preferably within the range of 65 to 100°C, and further preferably within the range of 70 to 90°C.

[0312] As the above-mentioned clear coating composition, any known thermosetting clear coating composition for coating automobile bodies, etc. can be used. As the thermosetting clear coating composition, for example, an organic solvent-based thermosetting coating composition containing a base resin having a crosslinkable functional group and a curing agent, an aqueous thermosetting coating composition, a powder thermosetting coating composition, etc. can be mentioned. Among them, from the viewpoint of the finished appearance of the multi-layer coating film formed, an organic solvent-based thermosetting coating composition containing a base resin having a crosslinkable functional group and a crosslinking agent is preferred.

[0313] Examples of the crosslinkable functional group of the base resin include a carboxyl group, a hydroxyl group, an epoxy group, a silanol group, etc. Examples of the type of base resin include an acrylic resin, a polyester resin, an alkyd resin, a urethane resin, an epoxy resin, a fluororesin, etc. Examples of the curing agent include a polyisocyanate compound, a blocked polyisocyanate compound, a melamine resin, a urea resin, a carboxyl group-containing compound, a carboxyl group-containing resin, an epoxy group-containing resin, an epoxy group-containing compound, etc.

[0314] Preferred combinations of base resin / curing agent for the above clear coating composition include a hydroxyl group-containing resin / polyisocyanate compound, a carboxyl group-containing resin / epoxy group-containing resin, a hydroxyl group-containing resin / blocked polyisocyanate compound, a hydroxyl group-containing resin / melamine resin, etc., and a hydroxyl group-containing resin / polyisocyanate compound is more preferred.

[0315] The clear coating composition may be a one-liquid type coating material, or a multi-liquid type coating material such as a two-liquid type urethane resin coating material.

[0316] Furthermore, the above-mentioned clear coating composition may contain coloring pigments, luster pigments, dyes, etc., to the extent that transparency is not impaired, and may further contain appropriate amounts of extender pigments, ultraviolet absorbers, light stabilizers, defoamers, thickeners, rust inhibitors, surface conditioners, etc.

[0317] The coating method of the clear coating composition is not particularly limited, but for example, a wet coating film can be formed by a coating method such as air spray coating, airless spray coating, rotary atomization coating, curtain coating, etc. In these coating methods, electrostatic application may be performed as necessary. Among these, air spray coating or rotary atomization coating is particularly preferred. The coating amount of the clear coating composition is usually preferably an amount that results in a cured film thickness of 10 to 70 μm, more preferably an amount that results in a cured film thickness of 20 to 50 μm.

[0318] Furthermore, when air spray coating, airless spray coating, or rotary atomization coating is performed, it is preferable to appropriately adjust the viscosity of the clear coating composition using a solvent such as an organic solvent so that it is within a viscosity range suitable for the coating, usually a viscosity range of about 15 to 60 seconds, particularly about 20 to 50 seconds, at 20°C using a Ford Cup No. 4 viscometer.

[0319] The heating can be performed by a known means, for example, a drying oven such as a hot air oven, an electric oven, or an infrared induction heating oven. The heating temperature is preferably within the range of 60 to 110° C., more preferably within the range of 65 to 100° C., and particularly preferably within the range of 70 to 90° C. The heating time is not particularly limited, but is preferably within the range of 10 to 40 minutes, and more preferably within the range of 20 to 40 minutes. EXAMPLES

[0320] The present invention will be described in more detail below with reference to Production Examples, Examples, and Comparative Examples. However, the present invention is not limited thereto. In each example, "parts" and "%" are based on mass unless otherwise specified. Furthermore, the thickness of the coating film is based on the cured coating film.

[0321] Production of urethane resin particles (A) Manufacturing Example 1 In a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser and a water separator, 70 parts of "ETERNACOLL UC-100" (trade name, manufactured by Ube Industries, a polycarbonate diol having an average molecular weight of 1000 and a cycloalkylene group having 6 carbon atoms), 30 parts of "PTMG3000" (trade name, manufactured by Mitsubishi Chemical Corporation, a polytetramethylene ether glycol having an average molecular weight of 3000 and a melting point of 21°C), 6.7 parts of dimethylolpropionic acid, 0.06 parts of "Neostan U-600" (trade name, manufactured by Nitto Kasei, a bismuth catalyst) and 28.0 parts of methyl ethyl ketone were charged and heated to 70°C with stirring, and then 33 parts of isophorone diisocyanate were added dropwise over 30 minutes, and stirring was continued while maintaining the temperature at 70°C, to obtain an NCO-terminated prepolymer having a free isocyanate group content of 8.0%. The reaction product obtained was cooled to 30°C, 4.1 parts of N-methylmorpholine and 150 parts of deionized water were added, emulsified, and then 18 parts of 5% diethylenetriamine aqueous solution was added thereto and stirred for 120 minutes to carry out a chain extension reaction. Next, methyl ethyl ketone was distilled off under reduced pressure and heating, and the concentration was adjusted with deionized water to obtain a urethane resin particle dispersion (A-1) having a solid content concentration of 40%, an acid value of 20 mgKOH / g, an average particle size of 110 nm, a minimum film-forming temperature of 31°C, a glass transition temperature of 85°C, and a breaking elongation rate of 387% at -20°C. The minimum film-forming temperature was measured in accordance with JIS K 6828-2:2003 using a temperature gradient tester (manufactured by Rigaku Kogyosha) under conditions of a set temperature range of -25 to 90°C and a dry film thickness of 50 μm.

[0322] Manufacturing Examples 2 to 5 Urethane resin particle dispersions (A-2) to (A-5) were obtained in the same manner as in Production Example 1, except that the blending compositions in Production Example 1 were as shown in Table 1 below.

[0323] [Table 1]

[0324] In addition, (Note 1) to (Note 3) in the table have the following meanings. (Note 1) "ETERNACOLL UM-90 (3 / 1)": Trade name, manufactured by Ube Industries, a polycarbonate diol having an average molecular weight of 900, a melting point of 50±5°C, and a cycloalkylene group having 6 carbon atoms. (Note 2) "ETERNACOLL UH-200": Trade name, manufactured by Ube Industries, a polycarbonate diol with an average molecular weight of 2000 and a melting point of 50±3°C, and no cycloalkylene group. (Note 3) "PTMG2000": Product name, manufactured by Mitsubishi Chemical Corporation, polytetramethylene ether glycol with a number average molecular weight of 2000 and a melting point of 20°C.

[0325] Production of urethane resin particles (A') having a core-shell structure Production Example 6 In a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser and a water separator, 70 parts of "ETERNACOLL UC-100" (trade name, manufactured by Ube Industries, average molecular weight 1000, melting point 54±5°C, polycarbonate diol having a cycloalkylene group with 6 carbon atoms), 6.8 parts of dimethylolpropionic acid, 0.06 parts of "Neostan U-600" (trade name, manufactured by Nitto Kasei, bismuth catalyst) and 28 parts of methyl ethyl ketone were charged as the raw materials for the shell part, and the temperature was raised to 80°C with stirring, after which 22.8 parts of isophorone diisocyanate was added, and stirring was continued while maintaining the temperature at 80°C, to obtain an NCO-terminated prepolymer with a free isocyanate group content of 0.5%.

[0326] Next, 30.6 parts of "PTMG3000" (trade name, manufactured by Mitsubishi Chemical Corporation, polytetramethylene ether glycol with a number average molecular weight of 3000 and a melting point of 21°C), 10.6 parts of isophorone diisocyanate, and 28.0 parts of methyl ethyl ketone, which are raw materials for the core portion, were further added to this reaction product and stirred to obtain an NCO-terminated prepolymer with a free isocyanate group content of 7.9%. The resulting reaction product was cooled to 30°C, and 4.1 parts of N-methylmorpholine and 150 parts of deionized water were added to emulsify, followed by adding 20.0 parts of a 5% aqueous solution of diethylenetriamine to the mixture and stirring for 120 minutes to carry out a chain extension reaction. Next, methyl ethyl ketone was distilled off under reduced pressure and heating, and the concentration was adjusted with deionized water to obtain a urethane resin particle dispersion (A'-1) having a core-shell structure with a solids concentration of 40%, an acid value of 20 mg KOH / g, an average particle diameter of 120 nm, a minimum film-forming temperature of 31°C, a glass transition temperature of 80°C, and a breaking elongation at -20°C of 245%.

[0327] Manufacturing Examples 7-27 Urethane resin particle dispersions (A'-2) to (A'-22) were obtained in the same manner as in Production Example 6, except that the blending compositions in Production Example 6 were as shown in Table 2 below.

[0328] [Table 2]

[0329] [Table 3]

[0330] [Table 4]

[0331] [Table 5]

[0332] In addition, (Notes 4) to (Notes 6) in the table have the following meanings. (Note 4) "ETERNACOLL UM-90 (1 / 3)": Trade name, manufactured by Ube Industries, polycarbonate diol with an average molecular weight of 900 and a cycloalkylene group with 6 carbon atoms. (Note 5) "ETERNACOLL UH-100": Trade name, manufactured by Ube Industries, a polycarbonate diol having an average molecular weight of 1000, a melting point of 45±5°C, and no cycloalkylene group. (Note 6) "PTMG1000": Trade name, manufactured by Mitsubishi Chemical Corporation, polytetramethylene ether glycol with a number average molecular weight of 1000 and a melting point of 17°C.

[0333] Manufacturing Example 28 In a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser and a water separator, 70 parts of "ETERNACOLL UC-100" (trade name, manufactured by Ube Industries, average molecular weight 1000, melting point 54±5°C, polycarbonate diol having a cycloalkylene group with 6 carbon atoms), 6.8 parts of dimethylolpropionic acid, 0.06 parts of "Neostan U-600" (trade name, manufactured by Nitto Kasei, bismuth catalyst) and 28 parts of methyl ethyl ketone were charged as the raw materials for the shell part, and the temperature was raised to 80°C with stirring, after which 22.7 parts of isophorone diisocyanate was added, and stirring was continued while maintaining the temperature at 80°C, to obtain an NCO-terminated prepolymer with a free isocyanate group content of 0.5%.

[0334] Next, 31.2 parts of "PTMG3000" (trade name, manufactured by Mitsubishi Chemical Corporation, polytetramethylene ether glycol with a number average molecular weight of 3000 and a melting point of 21°C), 10.6 parts of isophorone diisocyanate, and 28.0 parts of methyl ethyl ketone, which are raw materials for the core portion, were further added to this reaction product and stirred to obtain an NCO-terminated prepolymer with a free isocyanate group content of 7.9%. The resulting reaction product was cooled to 30°C, and 4.4 parts of N-methylmorpholine and 186 parts of deionized water were added to emulsify, after which 19.3 parts of a 5% aqueous solution of 2-(2-aminoethylamino)ethanol was added thereto and stirred for 120 minutes to carry out a chain extension reaction. Next, methyl ethyl ketone was distilled off under reduced pressure and heating, and the concentration was adjusted with deionized water to obtain a urethane resin particle dispersion (A'-23) having a core-shell structure with a solid concentration of 40%, an acid value of 20 mg KOH / g, a hydroxyl value of 2.9 mg KOH / g, an average particle size of 120 nm, a minimum film-forming temperature of 31°C, a glass transition temperature of 80°C, and a breaking elongation at -20°C of 245%.

[0335] Production of urethane resin particles for base coat paint composition (Y) Manufacturing Example 29 A reaction vessel equipped with a thermometer, a stirrer, and a reflux condenser was charged with 316.0 parts of "PTMG1000" (trade name, manufactured by Mitsubishi Chemical Corporation, polytetramethylene ether glycol having a number average molecular weight of 1000 and a melting point of 17°C), 17.0 parts of 2,2-dimethylolpropionic acid, 21.9 parts of trimethylolpropane, 113.0 parts of isophorone diisocyanate, 0.19 parts of "Neostan U-600" (trade name, manufactured by Nitto Kasei Corporation, bismuth catalyst), and 235.0 parts of methyl ethyl ketone. The reaction system was then purged with nitrogen gas, and the mixture was reacted at 80°C with stirring to obtain an NCO-terminated urethane prepolymer having a free isocyanate group content of 3.2%. The resulting methyl ethyl ketone solution was cooled to 40°C and 764.5 g of deionized water containing 13.8 parts of N-methylmorpholine was added to emulsify, after which 96.4 parts of a 5% aqueous solution of N-(2-hydroxyethyl)ethylenediamine was added thereto and stirred for 120 minutes. The methyl ethyl ketone was then distilled off under reduced pressure and heating, and the concentration was adjusted with deionized water to obtain a urethane resin particle dispersion (Ur-1) with a solids concentration of 35%, an acid value of 15 mg KOH / g, a hydroxyl value of 12 mg KOH / g, an average particle size of 120 nm, a minimum film-forming temperature of -5°C, a glass transition temperature of -7°C, and an elongation at break of 200% at -20°C.

[0336] Preparation of Hydroxyl-Containing Polyester Resin (B'1) Manufacturing Example 30 In a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser and a water separator, 174 parts of trimethylolpropane, 327 parts of neopentyl glycol, 352 parts of adipic acid, 109 parts of isophthalic acid and 101 parts of 1,2-cyclohexanedicarboxylic anhydride were charged, and the temperature was raised from 160 ° C to 230 ° C over 3 hours, and the generated condensed water was distilled off by a water separator while maintaining the temperature at 230 ° C, and the reaction was continued until the acid value was 3 mg KOH / g or less. 59 parts of trimellitic anhydride was added to this reaction product, and an addition reaction was carried out at 170 ° C for 30 minutes, and then the mixture was cooled to 50 ° C or less, and N-methylmorpholine was added in an equivalent amount to the acid group to neutralize it, and deionized water was gradually added to obtain a hydroxyl group-containing polyester resin solution (B'1-1) with a solid content concentration of 45% and a pH of 7.2. The resulting hydroxyl-containing polyester resin had a hydroxyl value of 128 mgKOH / g, an acid value of 35 mgKOH / g and a weight average molecular weight of 13,000.

[0337] Preparation of hydroxyl-containing acrylic resin (B'2) Manufacturing Example 31 In a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube, and a dropping device, 70.7 parts of deionized water and 0.52 parts of "Aqualon KH-10" (trade name, Daiichi Kogyo Seiyaku Co., Ltd., emulsifier, active ingredient 97%) were charged, and the mixture was stirred and mixed in a nitrogen stream and heated to 80 ° C. Then, 1% of the total amount of the monomer emulsion described below and 5 parts of a 6% aqueous solution of ammonium persulfate were introduced into the reaction vessel and held at 80 ° C. for 15 minutes. Thereafter, the remaining monomer emulsion was dropped into the reaction vessel held at the same temperature over 3 hours, and after the end of the dropping, the mixture was aged for 1 hour, and then cooled to 30 ° C. while gradually adding 40 parts of a 5% aqueous solution of N-methylmorpholine to the reaction vessel, and the mixture was discharged while filtering through a 100-mesh nylon cloth, to obtain an aqueous dispersion of a hydroxyl-containing acrylic resin (B'2-1) with a solid content of 45%. The resulting hydroxyl-containing acrylic resin (B'2-1) had a hydroxyl value of 43 mgKOH / g and an acid value of 12 mgKOH / g.

[0338] Monomer emulsion: 50 parts of deionized water, 10 parts of styrene, 40 parts of methyl methacrylate, 35 parts of ethyl acrylate, 3.5 parts of n-butyl methacrylate, 10 parts of 2-hydroxyethyl methacrylate, 1.5 parts of acrylic acid, 1.0 part of "Aqualon KH-10" and 0.03 parts of ammonium persulfate were mixed and stirred to obtain a monomer emulsion.

[0339] Manufacturing Example 32 A reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube, and a dropping device was charged with 130 parts of deionized water and 0.52 parts of "Aqualon KH-10" (trade name, Daiichi Kogyo Seiyaku Co., Ltd., emulsifier, active ingredient 97%), and the mixture was stirred and mixed in a nitrogen stream and heated to 80°C.

[0340] Next, 1.72 parts of the following monomer emulsion (1) and 5.3 parts of a 6% aqueous solution of ammonium persulfate were introduced into the reaction vessel and kept at 80°C for 15 minutes. After that, the remaining monomer emulsion (1) was dropped into the reaction vessel kept at the same temperature over 3 hours, and aging was carried out for 1 hour after the end of the dropwise addition. Then, the following monomer emulsion (2) was dropped over 1 hour, and after aging for 1 hour, 20 parts of a 5% aqueous solution of N-methylmorpholine was gradually added to the reaction vessel while cooling to 30°C, and the mixture was discharged while filtering through a 100-mesh nylon cloth, to obtain an aqueous dispersion of a hydroxyl-containing acrylic resin (B'2-2) with a solid content concentration of 30%. The obtained hydroxyl-containing acrylic resin (B'2-2) had an acid value of 16 mgKOH / g, a hydroxyl value of 66 mgKOH / g, and a glass transition temperature of 21°C.

[0341] Monomer emulsion (1): 42 parts of deionized water, 0.72 parts of "Aqualon KH-10", 2 parts of methylenebisacrylamide, 5 parts of styrene, 15 parts of methyl methacrylate, 5 parts of 2-hydroxyethyl methacrylate, and 23 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion (1).

[0342] Monomer emulsion (2): 42 parts of deionized water, 0.72 parts of "Aqualon KH-10", 0.05 parts of ammonium persulfate, 2.5 parts of methacrylic acid, 10 parts of 2-hydroxyethyl methacrylate, 5 parts of styrene, 12.5 parts of methyl methacrylate, 10 parts of n-butyl acrylate and 10 parts of n-butyl methacrylate were mixed and stirred to obtain a monomer emulsion (2).

[0343] Manufacturing Example 33 A reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube, and a dropping device was charged with 130 parts of deionized water and 0.52 parts of "Aqualon KH-10" (trade name, Daiichi Kogyo Seiyaku Co., Ltd., emulsifier, active ingredient 97%), and the mixture was stirred and mixed in a nitrogen stream and heated to 80°C.

[0344] Next, 1.72 parts of the monomer emulsion (1) and 5.3 parts of a 6% aqueous solution of ammonium persulfate were introduced into the reaction vessel and kept at 80°C for 15 minutes. After that, 35.4 parts of the monomer emulsion (1) were dropped into the reaction vessel kept at the same temperature over 1 hour, and immediately after the dropwise addition, the remaining 55.6 parts of the monomer emulsion (1) were started to be dropped into the reaction vessel. At the same time, 55.6 parts of the monomer emulsion (2) were dropped into the monomer emulsion (1), and the dropwise addition of the monomer emulsion (1) and the monomer emulsion (2) was completed over 2 hours. Then, 37.17 parts of the remaining monomer emulsion (2) was dropped into the reaction vessel over 1 hour, and after aging for 1 hour, 20 parts of a 5% N-methylmorpholine aqueous solution was gradually added to the reaction vessel while cooling to 30°C, and then the mixture was discharged while filtering through a 100-mesh nylon cloth to obtain an aqueous dispersion of hydroxyl-containing acrylic resin (B'2-3) with a solid content concentration of 30%. The obtained hydroxyl-containing acrylic resin (B'2-3) had an acid value of 16 mg KOH / g, a hydroxyl value of 66 mg KOH / g, and a glass transition temperature of 21°C. The above hydroxyl-containing acrylic resin (B'2-3) corresponds to the hydroxyl-containing acrylic resin particles (B'21) having a core-shell structure including the gradient polymer layer.

[0345] Monomer emulsion (1): 42 parts of deionized water, 0.72 parts of "Aqualon KH-10", 2 parts of methylenebisacrylamide, 5 parts of styrene, 15 parts of methyl methacrylate, 5 parts of 2-hydroxyethyl methacrylate, and 23 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion (1).

[0346] Monomer emulsion (2): 42 parts of deionized water, 0.72 parts of "Aqualon KH-10", 0.05 parts of ammonium persulfate, 2.5 parts of methacrylic acid, 10 parts of 2-hydroxyethyl methacrylate, 5 parts of styrene, 12.5 parts of methyl methacrylate, 10 parts of n-butyl acrylate and 10 parts of n-butyl methacrylate were mixed and stirred to obtain a monomer emulsion (2).

[0347] Production of blocked polyisocyanate compounds Manufacturing Example 34 A reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube, and a dropping device was charged with 1650 parts of "Sumidur N-3300" (trade name, manufactured by Sumika Bayer Urethane Co., Ltd., isocyanurate structure-containing polyisocyanate derived from hexamethylene diisocyanate, solid content concentration 100%, isocyanate group content 21.8%), 1100 parts of "PTMG2000" (trade name, manufactured by Mitsubishi Chemical Corporation, polytetramethylene ether glycol, average molecular weight 2,000, solid content concentration 100%), and 0.9 parts of 2,6-di-t-butyl-4-methylphenol, mixed well, and heated at 130 ° C. for 3 hours under a nitrogen stream. Next, 1200 parts of ethyl acetate and 1200 parts of diisopropyl malonate were charged, and 14 parts of a 28% methanol solution of sodium methoxide was added while stirring under a nitrogen stream, and the mixture was stirred at 65 ° C. for 8 hours. Next, the mixture was diluted with ethyl acetate so that the final solid concentration became 70%, to obtain a blocked polyisocyanate compound (C-1) having a solid concentration of 70% and a weight average molecular weight of 40,000.

[0348] Production of phosphoric acid-containing acrylic resin Manufacturing Example 35 A mixed solvent of 27.5 parts of methoxypropanol and 27.5 parts of isobutanol was placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser and a dropping device, and heated to 110 ° C. Then, 25 parts of styrene, 27.5 parts of n-butyl methacrylate, 20 parts of "isostearyl acrylate" (trade name, manufactured by Osaka Organic Chemical Industry Co., Ltd., branched higher alkyl acrylate), 7.5 parts of 4-hydroxybutyl acrylate, 15 parts of the following phosphoric acid group-containing polymerizable monomer, 12.5 parts of 2-methacryloyloxyethyl acid phosphate, 10 parts of isobutanol and 4 parts of t-butyl peroxy octanoate were added to the mixed solvent over 4 hours, and a mixture of 0.5 parts of t-butyl peroxy octanoate and 20 parts of isopropanol was added dropwise for 1 hour. After that, the mixture was stirred and aged for 1 hour to obtain a phosphoric acid group-containing acrylic resin solution (R-1) with a solid content concentration of 50%. The acid value due to the phosphate group of this resin was 83 mgKOH / g, the hydroxyl value was 29 mgKOH / g, and the weight average molecular weight was 10,000.

[0349] Phosphate-containing polymerizable monomer: 57.5 parts of monobutyl phosphate and 41 parts of isobutanol were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser and a dropping device, and the temperature was raised to 90°C. Then, 42.5 parts of glycidyl methacrylate were dropped over 2 hours, and the mixture was further stirred and aged for 1 hour. Then, 59 parts of isopropanol were added to obtain a phosphate-containing polymerizable monomer solution with a solid content concentration of 50%. The acid value of the resulting monomer due to the phosphate group was 285 mgKOH / g.

[0350] Pigment dispersion manufacturing Manufacturing Example 36 44.4 parts (20 parts solids) of the hydroxyl-containing polyester resin solution (B'1-1) obtained in Production Example 30, 90 parts of "JR-806" (trade name, Teika Co., Ltd., rutile-type titanium dioxide), 30 parts of "Variace B-35" (trade name, Sakai Chemical Industry Co., Ltd., barium sulfate powder), 0.8 parts of "Carbon MA100" (trade name, Mitsubishi Chemical Co., Ltd., carbon black), and 10 parts of deionized water were mixed and adjusted to pH 8.0 with 2-(dimethylamino)ethanol. Next, the resulting mixture was placed in a wide-mouth glass bottle, glass beads with a diameter of about 1.3 mm were added as a dispersion medium, and the bottle was sealed, and the mixture was dispersed for 30 minutes using a paint shaker to obtain a pigment dispersion (P-1).

[0351] Manufacturing Example 37 In a container equipped with a stirrer, 44.4 parts (20 parts solids) of the hydroxyl-containing polyester resin solution (B'1-1) obtained in Production Example 30, 10 parts of "Carbon MA-100" (trade name, Mitsubishi Chemical Corporation, carbon black), and 50 parts of deionized water were placed and mixed uniformly, and 0.5 parts of N-ethylmorpholine was added to the mixed solution to adjust the pH to 7.5. The resulting mixed solution was then placed in a wide-mouth glass bottle, glass beads with a diameter of about 1.3 mm were added as a dispersion medium, and the bottle was sealed. The mixture was dispersed for 4 hours using a paint shaker to obtain a pigment dispersion (P-2).

[0352] Preparation of water-based coating composition Example 1 165.2 parts (140.8 parts solids) of the pigment dispersion (P-1) obtained in Production Example 36, 62.5 parts (25 parts solids) of the urethane resin particle dispersion (A-1) obtained in Production Example 1, 83.3 parts (25 parts solids) of the hydroxyl group-containing acrylic resin solution (B'2-3) obtained in Production Example 33, 28.6 parts (20 parts solids) of the blocked polyisocyanate compound (C-1) obtained in Production Example 34, and 12.5 parts (10 parts solids) of "Cymel 325" (product name, manufactured by Allnex Japan, methyl / butyl mixed etherified melamine resin, solids concentration 80%) were uniformly mixed. Next, "UH-752" (product name, thickener, manufactured by ADEKA Corporation), N-methylmorpholine and deionized water were added to the obtained mixture to obtain aqueous coating composition No. 1 having a pH of 8.0, a coating solids concentration of 48%, and a viscosity of 30 seconds according to Ford Cup No. 4 at 20°C.

[0353] Examples 2 to 27, Comparative Examples 1 to 7 Water-based coating compositions Nos. 2 to 34 having a viscosity of 30 seconds as measured by Ford cup No. 4 at 20° C. were obtained in the same manner as in Example 1, except that the blending compositions were as shown in Table 3 below.

[0354] [Table 6]

[0355] [Table 7]

[0356] [Table 8]

[0357] [Table 9]

[0358] [Table 10]

[0359] In addition, (Note 7) in the table has the following meaning: (Note 7) "Bayhydur VPLS2310": Product name, manufactured by Sumika Bayer Urethane Co., Ltd., blocked polyisocyanate compound, solids concentration 38% Preparation of base coat paint composition (Y-1) Manufacturing Example 38 104.7 parts of the pigment dispersion (P-2) obtained in Production Example 37, 100 parts (30 parts solids) of the hydroxyl-containing acrylic resin (B'2-3) obtained in Production Example 33, 57.1 parts (20 parts solids) of the urethane resin particle dispersion (Ur-1) obtained in Production Example 29, 42.9 parts (30 parts solids) of the blocked polyisocyanate compound (C-1) obtained in Production Example 34, and 4 parts (2 parts solids) of the phosphoric acid-containing acrylic resin solution (R-1) obtained in Production Example 35 were uniformly mixed. Next, "UH-752" (trade name, manufactured by ADEKA Corporation, thickener), N-methylmorpholine and deionized water were added to the obtained mixture to obtain a base coat paint composition (Y-1) having a pH of 7.7, a paint solids concentration of 25%, and a viscosity of 30 seconds according to Ford Cup No. 4 at 20 ° C.

[0360] Manufacturing Examples 39-43 Base coat paint compositions (Y-2) to (Y-6) were obtained in the same manner as in Production Example 38, except that the blending compositions in Production Example 38 were as shown in Table 4 below.

[0361] [Table 11]

[0362] In addition, (Note 7) in the table has the following meaning: (Note 7) "Bayhydur VPLS2310": Product name, manufactured by Sumika Bayer Urethane Co., Ltd., blocked polyisocyanate compound, solids concentration 38% Preparation of test specimens A thermosetting epoxy resin-based cationic electrodeposition coating composition (product name "Elecron GT-10", manufactured by Kansai Paint Co., Ltd.) was electrodeposited onto a zinc phosphate-treated cold-rolled steel sheet to a film thickness of 20 μm, and then heated at 170° C. for 30 minutes to be cured. Thus, a coated object was prepared in which an electrodeposition coating film was formed on a steel sheet.

[0363] Example 28 Preparation of test coated panels The aqueous coating composition No. 1 obtained in Example 1 was electrostatically coated on the above test substrate as the colored coating composition (X) using a rotary atomizing electrostatic coater so that the dry film thickness was 25 μm, and the coating was left for 5 minutes. Next, the base coat coating composition (Y) obtained in Production Example 38 was electrostatically coated on the uncured colored coating film as the base coat coating composition (Y-1) using a rotary atomizing electrostatic coater so that the dry film thickness was 15 μm, and the coating was left for 5 minutes, and then preheated at 80 ° C. for 3 minutes. Furthermore, "Soflex # 520 Clear" (trade name, manufactured by Kansai Paint Co., Ltd., a two-liquid type acrylic urethane organic solvent type clear coating containing a hydroxyl group-containing acrylic resin and a polyisocyanate compound) (Z-1) was electrostatically coated on the base coat coating film as the clear coat coating composition (Z) so that the dry film thickness was 35 μm, and the coating was left for 7 minutes. Next, the first colored coating film, the second colored coating film and the clear coating film were heat-cured by heating at 80° C. for 30 minutes to prepare a test coated plate.

[0364] Examples 29 to 59, Comparative Examples 8 to 14 Each coated test plate was prepared in the same manner as in Example 28, except that the type of aqueous coating composition was changed as shown in Table 5 below.

[0365] Each of the test coated panels obtained above was evaluated by the following test methods. The evaluation results are shown in Table 5 below.

[0366] Test Method Glass adhesion A urethane adhesive (product name "3740", manufactured by Sunstar Inc., automobile windshield agent) was further applied to each test coated plate obtained in the above Examples and Comparative Examples so that the coating shape was 20 mm wide, 3 mm thick, and 100 mm long or more, and after covering with release paper, it was pressed evenly with a flat plate. After removing the flat plate, it was left to harden for 72 hours at a temperature of 23±2°C and a humidity of 50±5%. Then, the release paper was peeled off. Next, each test coated plate was immersed in a thermostatic water bath set at 50°C for 240 hours, and then immersed in water at 23°C for 1 hour to cool, and the following peel test was performed. The hardened adhesive layer was pulled by hand in a direction at least 90 degrees to the coating, and cut with a cutter knife at 2-3 mm intervals at an angle of about 60 degrees to the coating, until it reached the surface of the coating. The peeling condition after peeling the adhesive layer was evaluated according to the following criteria. S, A, and B are acceptable. S: No peeling of the adhesive layer was observed, and no exposure of the coating film was observed. A: The coating film is not destroyed, and only the adhesive layer undergoes cohesive failure and peels off, but the adhesion between the coating film and the adhesive layer is almost maintained. B: The coating film peeled off due to cohesive failure, and the width of the peeling was less than 1 mm from the part cut with the cutter knife. C: The coating film peeled off due to cohesive failure, and the width of the peel was 1 mm or more from the part where the cutter knife was inserted. D: Peeling was observed at the interface between the coating film and the adhesive layer.

[0367] Sharpness For each of the test coated panels obtained in the above Examples and Comparative Examples, the image sharpness was evaluated according to the following criteria based on the Short Wave (SW) value measured using a "Wave Scan" (product name, manufactured by BYK Gardner). The smaller the SW value, the higher the image sharpness of the coating surface. S, A, and B are acceptable. S:SW value was less than 8, A: SW value was 8 or more and less than 10. B: SW value was 10 or more and less than 15. C: SW value was 15 or more and less than 20. D: SW value was 20 or more.

[0368] Chipping resistance Each test coated plate obtained in the above Examples and Comparative Examples was placed on the specimen holder of a stone chipping tester "JA-400 type" (product name, manufactured by Suga Test Instruments, chipping resistance test device), and 50 g of crushed granite stone with grain size No. 7 was collided with the test coated plate at an angle of 45 degrees from a distance of 30 cm at 0°C using compressed air of 0.39 MPa (4 kgf / cm2). The test coated plate obtained was then washed with water, dried, and a cloth adhesive tape (manufactured by Nichiban Co., Ltd.) was applied to the coating surface, which was then peeled off. The degree of scratches on the coating film was visually observed and evaluated according to the following criteria. S, A, and B are acceptable. A: The size of the scratches is extremely small, and the electroplated surface or the base steel sheet is not exposed. B: The size of the scratches is small, and the electroplated surface or the base steel sheet is not exposed. C: The size of the scratch is small, but the electroplated surface or the base steel sheet is exposed. D: The size of the scratch is quite large, and the electroplated surface or the base steel sheet is exposed. E: The scratch is quite large, and a large portion of the base steel sheet is exposed.

[0369] [Table 12]

[0370] [Table 13]

[0371] [Table 14]

[0372] [Table 15]

[0373] [Table 16]

Claims

1. The present invention comprises urethane resin particles (A), a reactive group-containing resin (B), and a crosslinking agent (C), each of which has a minimum film-forming temperature in the range of −20 to 50° C. and a glass transition temperature in the range of 60 to 120° C. as determined by dynamic viscoelasticity measurement at a frequency of 1 Hz, The aqueous coating composition, wherein the reactive group-containing resin (B) comprises at least one resin selected from the group consisting of acrylic resins, polyester resins, and acrylic-modified polyester resins.

2. 2. The aqueous coating composition according to claim 1, wherein the urethane resin particles (A) have a breaking elongation at -20°C within the range of 200 to 350%.

3. 3. The aqueous coating composition according to claim 1, wherein the polyol component (a1) of the urethane resin particles (A) comprises a polyol component (A1) having a melting point of 40 to 80°C.

4. 4. The aqueous coating composition according to claim 1, wherein the polyol component (a1) of the urethane resin particles (A) comprises a polycarbonate polyol (a1-1).

5. The aqueous coating composition according to any one of claims 1 to 4, comprising, as the polyol component (a1) of the urethane resin particles (A), a polycarbonate diol obtained from a diol component containing an alicyclic diol having a cycloalkylene group having 6 or more carbon atoms.

6. 6. The aqueous coating composition according to claim 1, wherein the urethane resin particles (A) are urethane resin particles (A') having a core-shell structure.

7. 7. The aqueous coating composition according to claim 6, wherein the polyol component (a'1-I) of the urethane resin constituting the core of the urethane resin particles (A') having a core-shell structure comprises a polyether polyol (a1-2).

8. The aqueous coating composition according to claim 6 or 7, comprising a polycarbonate polyol (a1-1) as the polyol component (a'1-II) of the urethane resin constituting the shell portion of the urethane resin particles (A') having a core-shell structure.

9. The aqueous coating composition according to any one of claims 6 to 8, wherein the mass ratio (a'1-I) / (a'1-II) of the polyol component (a'1-I) of the urethane resin constituting the core part and the polyol component (a'1-II) of the urethane resin constituting the shell part of the urethane resin particles (A') having a core-shell structure is within the range of 60 / 40 to 20 / 80.

10. 10. The aqueous coating composition according to claim 1, wherein the reactive group-containing resin (B) comprises a hydroxyl group-containing resin (B').

11. The aqueous coating composition according to any one of claims 1 to 10, wherein the crosslinking agent (C) comprises at least one crosslinking agent selected from an amino resin, a polyisocyanate compound, and a blocked polyisocyanate compound.

12. A method for forming a coating film, comprising: applying the aqueous coating composition according to any one of claims 1 to 11 onto a substrate to form an uncured colored coating film; and then heating the uncured colored coating film at a temperature within the range of 60 to 110°C to cure it.

13. Step (II-1): A step of applying a colored coating composition (X) to a substrate to form an uncured colored coating film; Step (II-2): A step of applying a base coat paint composition (Y) onto the uncured colored coating film to form an uncured base coat coating film; Step (II-3): A step of applying a clear coat paint composition (Z) onto the uncured base coat film to form an uncured clear coat film; and Step (II-4): A method for forming a multilayer coating film, comprising a step of heating the uncured colored coating film, the uncured base coat coating film, and the uncured clear coat coating film to simultaneously cure them, comprising the step of: A method for forming a multi-layer coating film, wherein the aqueous coating composition according to any one of claims 1 to 11 is used.

14. The method for forming a multilayer coating film according to claim 13, wherein the heating temperature in the step (II-4) is within the range of 60 to 110°C.

Citation Information

Patent Citations

  • Thermosetting composition

    JP1992018412A

  • Polyurethane-based emulsion for water-based coating material and water-based coating using the same

    JP1999323252A

  • Water-based coating composition and coating method by using the same

    JP2005089613A

  • Aqueous polyurethane resin dispersion and use thereof

    JP2019059863A

  • Multi-layer coating film forming method

    JP2019198861A